Lithium-ion cells with high performance electrolytes and silicon oxide active materials that achieve extremely long cycle life performance

By using a combination of high-content silicon oxide and graphite in the negative electrode of lithium-ion batteries, and combining nano-scale conductive carbon and polymer binding agent, the structural damage caused by volume expansion during the circulation process is solved, and efficient long-life cycle performance is achieved.

JP2025060873AActive Publication Date: 2025-04-10IONBLOX INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024229830
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-08-30
Filing Date
2024-12-26
Publication Date
2025-04-10
Estimated Expiration
2040-06-19

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, high-capacity negative electrode materials such as silicon oxides lead to structural damage due to lithium dielectric alloying and volume expansion during the circulation process, reducing cycling efficiency.

Method used

The negative electrode is composed of 75% to 92% of the active material, 1% to 7% of the nanoscale conductive carbon and 6% to 20% of the polymer binding agent, where the active material consists of 35% to 95% of the silicon oxide material and 5% to 65% of the graphite, and anhydrous solvent electrolyte containing 5% to 25% of vinyl fluoride carbonate is used.

Benefits of technology

It realizes the long-life cycle performance of lithium-ion batteries with a capacity reduction of no more than 20% during 700 cycles, and is suitable for high-energy density applications such as electric vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060873000001_ABST
    Figure 2025060873000001_ABST
Patent Text Reader

Abstract

To provide a lithium-ion cell that achieves good cycling capability.SOLUTION: A lithium-ion cell includes a negative electrode having an active material having a silicon oxide-based material and graphite, a positive electrode, a separator, an electrolyte having a lithium salt and a non-aqueous solvent, and a container. The electrolyte provides unprecedented cycling performance for a battery having a negative electrode having a substantial amount of silicon-based active material to achieve high specific capacity. The electrolyte also uses a significant amount of fluoroethylene carbonate solvent, and appropriately selects other solvent components such as dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate to exclude other unstable components and provide stability.SELECTED DRAWING: Figure 24
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Patent Application Publication No. 16 / 556,670 to Dong et al., entitled “Lithium Ion Cells With High Performance Electrolyte And Silicon Oxide Active Materials Achieving Very Long Cycle Life Performance,” and to U.S. Provisional Patent Application No. 62 / 866,978 to Dong et al., entitled “Lithium Ion Cells With High Performance Electroyte And Silicon Oxide Active Materials Achieving Very Long Cycle Life Performance,” filed June 26, 2019, both of which are incorporated herein by reference.

[0002] Federally Funded Research and Development This invention was made with Government support under United States Government Funding Agreement No. DE-EE0006250 under United States Advanced Battery Consortium Program Number: 18-2216-ABC awarded by the U.S. Department of Energy. The Government has certain rights in this invention.

[0003] The present invention relates to the formation of cells having electrolytes that have been discovered to function with negative electrodes incorporating high capacity silicon oxide active materials while achieving good cycling capabilities. [Background technology]

[0004] Lithium batteries are widely used in consumer electronics due to their relatively high energy density. For some current commercially available batteries, the anode material can be graphite, and the cathode material can include lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), lithium nickel oxide (LiNiO2), lithium nickel cobalt oxide (LiNiCoO2), lithium nickel cobalt manganese oxide (LiNiMnCoO2), lithium nickel cobalt aluminum oxide (LiNiCoAlO2), etc. For the anode, lithium titanate is an alternative to graphite with good cycling properties, but with a lower energy density. Other alternatives to graphite, such as tin oxide and silicon, have the potential to provide increased energy density. However, some high capacity anode materials have been found to be commercially unsuitable due to high irreversible capacity losses and poor discharge and charge cycles associated with the structural changes and very large volume expansion associated with the intercalation / alloying of lithium, especially for silicon. Structural changes and large volume changes can compromise the structural integrity of the electrode, which can reduce cycling efficiency. Summary of the Invention [Means for solving the problem]

[0005] In a first aspect, the present invention provides a method for producing a composition comprising the steps of: a negative electrode comprising about 75% to about 92% by weight of an active material, about 1% to about 7% by weight of nanoscale conductive carbon, and about 6% to about 20% by weight of a polymer binder, the active material comprising about 35% to about 95% by weight of a silicon oxide based material and about 5% to about 65% by weight of graphite; Formula LiNi x Mn y Co za positive electrode comprising a lithium nickel cobalt manganese oxide generally represented by the formula: O2, where x+y+z≈1, 0.3≦x, 0.025≦y≦0.35, and 0.025≦z≦0.35, a conductive carbon, and a polymer binder; a separator between the negative and positive electrodes; an electrolyte comprising about 1 M to about 2 M lithium salt and a non-aqueous solvent, the non-aqueous solvent comprising at least about 5 volume percent fluoroethylene carbonate and at least about 25 volume percent combined amounts of dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate; A container that encloses the other cell components; The present invention relates to a lithium ion cell comprising:

[0006] In a further aspect, the present invention provides a method for producing a method for the treatment of a cancer a negative electrode comprising about 75% to about 92% by weight of an active material, about 1% to about 7% by weight of nanoscale conductive carbon, and about 6% to about 20% by weight of a polymer binder, the active material comprising about 40% to about 95% by weight of a silicon oxide based material and about 5% to about 60% by weight of graphite; Formula LiNi x M y Co z a positive electrode comprising a nickel-rich lithium nickel cobalt metal oxide, generally represented by the formula: O2, where x+y+z≈1, 0.3≦x, 0.025≦y≦0.35, 0.025≦z≦0.35, and M is Mn, Al, Mg, Sr, Ba, Cd, Zn, Ga, B, Zr, Ti, Ca, Ce, Y, Nb, Cr, Fe, V, or combinations thereof, a conductive carbon, and a polymer binder; a separator between the negative and positive electrodes; an electrolyte comprising about 1 M to about 2 M lithium salt and a non-aqueous solvent, the non-aqueous solvent comprising at least about 5 volume percent fluoroethylene carbonate and at least about 25 volume percent combined amounts of dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate; A container that encloses the other cell components; The present invention relates to a lithium ion cell comprising:

[0007] In some embodiments, the lithium-ion cell can be cycled at a charge rate of 1C and a discharge rate of 1C for at least about 700 cycles without a capacity drop of more than 20% relative to the third cycle capacity. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a close-up view of a pouch battery having a battery core separated from a two-part pouch case. [Diagram 2] FIG. 2 is a perspective bottom view of the assembled pouch battery of FIG. [Diagram 3] FIG. 3 is a bottom view of the pouch battery of FIG. 2. [Figure 4] 1 illustrates an embodiment of a battery core including an electrode stack. [Diagram 5] FIG. 11 is a combination of plots of specific discharge capacity as a function of cycle number for three coin cell formats with a negative electrode based on a blend of silicon oxide / carbon composite particles and graphite and a positive electrode based on LiNiO.6MnO.2CoO.2O2 (NMC622) or LiNiO.8MnO.1CoO.1O2 (NMC811) cycled over the voltage range of 4.35V to 2.5V or 4.30V to 2.5V (NMC622) or 4.20V to 2.5V (NMC811), with initial discharge capacities obtained in the order listed from highest to lowest. [Figure 6] 6 is a combination plot of normalized specific discharge capacity as a function of cycle number for the three coin cells used to create the results plotted in FIG. 5. [Figure 7] FIG. 1 is a plot of normalized capacity as a function of cycle number for coin cells cycled at 1C charge / discharge rate with NMC622 positive electrode active material and SiO composite / graphite mixed negative electrode active material formed with six different electrolytes, two of which contain ethylene carbonate and four of which do not contain ethylene carbonate. [Figure 8] FIG. 8 is a plot of normalized capacity as a function of cycle number for five coin cells identical to those used in FIG. 7, except that they were cycled at a charge / discharge rate of 2C. [Figure 9] FIG. 8 is a plot of normalized capacity as a function of cycle number for coin cells cycled at a charge / discharge rate of 1C, where the cells were formed as shown in FIG. 7, except that one of the six electrolytes had various amounts of fluoroethylene carbonate as shown in Table 3. [Figure 10] FIG. 10 is a plot of non-normalized specific capacity referenced relative to the positive electrode active material weight corresponding to the plot in FIG. [Figure 11] FIG. 8 is a plot of normalized capacity as a function of cycle number for coin cells cycled at a charge / discharge rate of 1C, where the cells were formed as shown in FIG. 7, except that one of the six electrolytes had various amounts of dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate as shown in Table 3. [Figure 12] FIG. 12 is a plot of normalized capacity as a function of cycle number for a coin cell equivalent to that used in FIG. 11, except that the cell was cycled at a charge / discharge rate of 2C. [Figure 13] FIG. 8 is a plot of normalized capacity as a function of cycle number for coin cells cycled at a charge / discharge rate of 1C, where the cells were formed as shown in FIG. 7 except that one of three electrolytes was used with optional additives. [Figure 14] FIG. 14 is a plot of non-normalized specific capacity referenced relative to the positive electrode active material weight corresponding to the plot in FIG. 13. [Figure 15] FIG. 8 is a plot of normalized capacity as a function of cycle number for a coin cell formed with NMC811 positive electrode active material and the same negative electrode as used in the cell of FIG. 7, where the electrolyte is electrolyte 2 from Table 3, cycled at a charge / discharge rate of 1C. [Figure 16]FIG. 17 is a plot of normalized capacity as a function of cycle number for a coin cell equivalent to that used in FIG. 15, except that the cycles were performed at a charge / discharge rate of 2C. [Figure 17] FIG. 1 is a front view of a pouch cell designed for operation at approximately 11 Ah. [Figure 18] FIG. 18 is a side view of the pouch cell of FIG. 17. [Figure 19] FIG. 13 is a plot of discharge capacity as a function of cycle number for two pouch cells using silicon oxide / carbon blended with graphite and NMC622 based positive electrodes cycled over a voltage range of 4.3V to 2.3V. [Figure 20] FIG. 20 is a plot of normalized discharge capacity as a function of cycle number for the two pouch cells used to generate the results in FIG. 19. [Figure 21] 1 is a plot of capacity as a function of cycles for a cell using a positive electrode with NMC811 active material and an improved silicon oxide-based anode described herein. [Figure 22] FIG. 22 is a plot of normalized capacity as a function of cycle for the cells used to create the plots of FIG. 21. [Diagram 23] FIG. 1 is a plot of normalized capacity as a function of cycles at 1C charge / discharge rate for pouch cells formed with NMC622 positive electrode active material, SiOx composite graphite mixture negative electrode active material, and one of the three electrolyte formulations from Table 3. [Figure 24] FIG. 24 is a plot of discharge capacity as a function of cycle number for the pouch cell used to create FIG. 23. [Diagram 25] FIG. 1 is a plot of normalized discharge capacity as a function of cycles for coin cells formed with positive electrodes having a blend of nickel-rich NCM and lithium and manganese-rich NCM and negative electrodes used in the examples, the plots being shown for five different electrolytes. [Figure 26]FIG. 26 is a plot of unnormalized discharge capacity as a function of cycle for the cells used to create FIG. 25. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] A new electrolyte composition has been discovered that provides unprecedented cycling performance for batteries that include negative electrodes with substantial amounts of silicon-based active materials to achieve high specific capacity. This achievement builds on previous work to provide substantial improvements in negative electrode design that provide a significant jump in cycling performance. The new electrolyte formulation uses a significant amount of fluoroethylene carbonate solvent and excludes other unstable components, and appropriately selects other solvent components to provide stability. In the negative electrode, the active material can be designed to include a blend with a silicon-based active material such as silicon oxide, but with a significant component of graphite. In addition, it has been discovered that binder characteristics provide a significant contribution to cycling stability. Previous work has obtained over 600 cycles before reaching 80% of the initial capacity for reasonable discharge rates and at high specific capacity. Further improved work herein has obtained over 800 cycles before reaching 80% of the initial capacity for reasonable discharge rates and at high specific capacity. The cycling performance improvement is a significant achievement for the use of batteries for electric vehicle applications.

[0010] Lithium is used in both primary and secondary batteries. Attractive features of lithium for cell or battery applications are its light weight and the fact that it is the most electropositive metal, and aspects of these features can be advantageously captured in lithium-based batteries. Certain forms of metals, metal oxides, and carbon materials are known to incorporate lithium ions from the electrolyte into their structure by intercalation, alloying, or similar mechanisms. The positive electrode of a lithium-based battery generally includes an active material that reversibly intercalates / alloys with lithium. A lithium-ion cell generally refers to a cell in which the negative electrode active material is also a lithium intercalation / alloying material. As used herein and for convenience, the terms cell and battery and variations thereof are used interchangeably, except where an explicit distinction is made.

[0011] The batteries described herein are lithium-ion batteries that use a non-aqueous electrolyte solution containing lithium cations and appropriate anions. For secondary lithium-ion batteries during charging, oxidation occurs at the cathode (positive electrode), where lithium ions are extracted and electrons are released. During discharging, reduction occurs at the cathode, where lithium ions are inserted and electrons are consumed. Similarly, during charging, reduction occurs at the anode (negative electrode), where lithium ions are taken up and electrons are consumed. Also, during discharging, oxidation occurs at the anode, where lithium ions and electrons are released. Unless otherwise specified, performance values ​​described herein are at room temperature, i.e., about 23±2° C.

[0012] The term "element" is used herein to mean an element that has the appropriate oxidation state when it is in a composition, and when it is shown to be in its elemental form, M 0 The term "metal" is used in the conventional manner to mean a member of the Periodic Table found in Table 1. A metal element therefore generally exists only in the metallic state of its elemental form or in a suitable alloy of the metal's elemental form. That is, metal oxides or other metal compositions other than metal alloys are generally not metals.

[0013] When using lithium-ion batteries, the uptake and release of lithium from the positive and negative electrodes induces changes in the structure of the electroactive materials. As long as these changes are essentially reversible, cycling does not change the capacity of the materials. However, it has been observed that cycling reduces the capacity of the active materials to a greater or lesser extent. Thus, after a number of cycles, the performance of the cell becomes less than acceptable and the cell is replaced. Also, the first cycle of the cell generally experiences an irreversible capacity loss that is significantly greater than the capacity loss per cycle in subsequent cycles. The irreversible capacity loss (IRCL) is the difference between the charge capacity and the first discharge capacity of a new cell. Positive electrodes based on lithium metal oxides may exhibit some IRCL, resulting in some replenishment of the negative electrode in terms of available lithium for cycling. Irreversible capacity loss may result in a corresponding decrease in the capacity, energy and power of the cell due to changes in the cell materials during the initial cycles.

[0014] Elemental silicon and other silicon-based active materials are of great interest as potential anode materials due to silicon's extremely high specific capacity for lithium uptake and release. Elemental silicon forms alloys with lithium, and is theoretically capable of having a lithium content corresponding to five or more lithium atoms per silicon atom (e.g., Li 4.4Silicon has a theoretical specific capacity of about 4000-4400 mAh / g, which is significantly greater than the theoretical capacity of about 370 mAh / g for graphite. Graphite is believed to intercalate lithium to a level of about one lithium atom per six carbon atoms (LiC6). Also, elemental silicon, silicon alloys, silicon composites, etc. may have a low potential relative to lithium metal similar to graphite. However, upon alloying with lithium, silicon undergoes a very large volume change. Large volume expansions of about 2-3 times the initial volume or more have been observed, and the large volume change is associated with a significant decrease in the cycling stability of batteries with silicon-based anodes. Silicon suboxide, i.e., SiO, where x<2, is a x It has also been found that silicon suboxide is a desirable active material for lithium-based batteries. It can have high specific capacity for lithium alloying in some embodiments. By referring to silicon suboxide, silicon dioxide can be recognized as a fully oxidized form of silicon. For convenience, silicon suboxide can be generally referred to as silicon oxide, which is not limited to silicon monoxide (SiO), unless otherwise indicated.

[0015] In a particularly interesting embodiment, the silicon-based active material may include elemental silicon and / or silicon suboxide as the main active material. Silicon suboxide has been found to be particularly effective in achieving long-term cycling stability. Carbon may be incorporated into the composite active material to stabilize the silicon-based active material and to enhance electrical conductivity. For carbon composites using nanoscale elemental silicon and / or silicon oxide, long-term cycling stability remains challenging, but the applicant has achieved adequate cycling stability for consumer electronics applications. Herein, long-term cycling stability is described based on a mixture of electroactive graphite and silicon-based composites, in addition to other electrode design improvements. As described in detail below, the stabilized silicon-based electrode may further include additional conductive sources such as nanoscale carbon and improved binder blends that also contribute significantly to cycling stability.

[0016] Although the improved electrode design significantly improves cycling performance, it has been discovered that further cycling stabilization can be achieved due to the improved electrolyte formulation. The improved electrolyte is based on a solvent comprising at least 5 volume percent fluoroethylene carbonate and at least 25 volume percent dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, or mixtures thereof. Additionally, in some embodiments, the electrolyte should be essentially free of ethylene carbonate. The electrolyte further comprises about 1M to about 2M electrolyte salt.

[0017] Fluorinated solvents have been found to be particularly useful for silicon-based active materials. Previous results have been obtained with commercially available electrolytes containing proprietary fluorinated solvents as described in co-pending U.S. Patent Application Publication No. 15 / 948,160 to Venkatachalam et al., currently published as U.S. Patent Application Publication No. 2019 / 0207209A1, entitled "Electrodes with Silicon Oxide Active materials for Lithium Ion Cells Achieving High Capacity, High Energy Density and Long Cycle Life Performance," which is incorporated herein by reference. The use of fluoroethylene carbonate as a suitable solvent for low temperature cell performance is recognized in U.S. Patent Application Publication No. 2013 / 0157147 to Li et al., entitled "Low Temperature Electrolyte for High Capacity Lithium Based Batteries," which is incorporated herein by reference (hereinafter the '147 application).

[0018] The use of fluoroethylene carbonate for the formation of solid electrolyte interphase layers is described in Markevich et al., "Fluoroethylene Carbonate as an Important Component for the Formation of an Effective Solid Electrolyte Interphase on Anodes and Cathodes for Advanced Li-Ion Batteries," ACS Energy letters 2017, 2, 1137-1345, which is incorporated herein by reference. Markevich's article suggests utility for silicon nanowire-based anodes. The focus of Markevich's article is the use of high voltage cathodes compared to ethylene carbonate-based electrolytes. This work extends the previous work of the '147 application in combination with superior electrode formation to achieve unprecedented silicon-based cell performance. In particular, this work demonstrates the effective use of FEC-based electrolytes for silicon oxide / graphite blend anodes at high loadings and commercially relevant electrode designs.

[0019] As used herein, active materials for lithium-ion secondary cells generally include, for example, a positive electrode (i.e., cathode) active material having a moderately high average voltage relative to lithium, and a silicon-based active material for the negative electrode (i.e., anode). In general, a variety of cathode materials can be used. For example, it is possible to use commercially available cathode active materials with existing available commercial products. Such cathode active materials include, for example, lithium cobalt oxide (LiCoO2), LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 LiNiCoAlO2 (L333 or NMC111), LiNiCoAlO2 (NCA), other lithium nickel manganese cobalt oxides (NMC), LiMn2O4 (lithium manganese oxide spinel), modified forms thereof or mixtures thereof.

[0020] Nickel-rich lithium nickel cobalt manganese oxide (LiNi x Mn y Co z O2, 0.45≦x, 0.05≦y, z≦0.35) may be of interest due to its lower cost and lower flammability risk versus lithium cobalt oxide, as well as its cycling capability at higher voltages. As a result, nickel-rich lithium nickel manganese cobalt oxide active materials combined with improved silicon-based anodes form cells with excellent cycling stability. Lithium metal oxide materials with high specific capacity that have a layered crystal structure and are lithium-rich relative to a LiMO2 (M=non-lithium metal) reference composition are also described, for example, in U.S. Pat. No. 8,389,160 to Venkatachalam et al., entitled "Positive Electrode Materials For Lithium Ion Batteries Having a High Specific Discharge Capacity And Processes for the Synthesis of These Materials" (hereinafter the '160 patent), and U.S. Pat. No. 8,465,873 to Lopez et al., entitled "Positive Electrode Materials for High Discharge Capacity Lithium Ion Batteries" (hereinafter the '873 patent), both of which are incorporated herein by reference. These materials can be described as high capacity manganese-rich compositions (HCMR™). Blends of lithium-rich + manganese-rich NMC and nickel-rich NMC positive electrode active material compositions can also be used.

[0021] In particular, the formula LiNi x Mn y Co zDesired cycling results can be obtained from nickel-rich lithium nickel manganese cobalt oxide (N-NMC), which can be represented by the formula: O2, where x≧0.3 and x+y+z≈1. Commercially available formulations of these compounds include, for example, LiNi 0.33 Mn 0.33 Co 0.33 O2 (BASF and Targray (Canada)), LiNi 0.5 Mn 0.3 Co 0.2 O2 (BASF), LiNi 0.6 Mn 0.2 Co 0.2 O2 (Targray (Canada), Umicore (Belgium) and L&F Company (Korea)), LiNi 0.8 Mn 0.1 Co 0.1 O2 (Targray, Canada, LG Chemical, Umicore (Belgium) and L&F Company (Korea). In the industry, NCM and NMC are listed in the order in which cobalt and manganese correspond, and both are used interchangeably herein and the presentation is equivalent and simply based on personal preference.

[0022] As mentioned above, silicon-based electrodes pose challenges in obtaining adequate cycling for commercial applications. For consumer electronics applications, a suitable cycling target may be about 250-450 cycles without unacceptable performance loss, but higher cycling stability is desirable for automotive and similar higher capacity applications. Applicants have achieved suitable cell designs for consumer electronics applications that can achieve adequate performance using silicon-based anodes. These batteries are described in U.S. Patent Application Publication No. 2015 / 0050535 to Amiruddin et al., entitled "Lithium Ion Batteries With High Capacity Anode Material and Good Cycling for Consumer Electronics" (hereinafter the '535 Application), which is incorporated herein by reference. The novel electrode designs herein provide cycling beyond the target cycling stability for consumer electronics and achieve adequate performance for automotive and other high capacity applications.

[0023] Similar to silicon, oxygen-deficient silicon oxides, such as silicon oxide, SiO x(0.1≦x≦1.9) is capable of intercalating / alloying with lithium so that the oxygen-deficient silicon oxide can function as an active material in a lithium-based cell. Silicon oxide can incorporate relatively large amounts of lithium so that the material can exhibit a large specific capacity. However, silicon oxide is also generally observed to have a capacity that degrades relatively quickly with cell cycling. Commercially available silicon-based materials, including SiO, which may be in composite with carbon and silicon nanocrystals from several sources, are available from Alfa Aesar (USA), Sigma-Aldrich (USA), Shin-Etsu (Japan), Osaka Titanium Corporation (Japan) and Nanostructured and Amorphous Materials Corp. (USA). Below, additional particularly suitable formulations of silicon-based compositions are further described. The applicant has achieved cycling stabilization of silicon oxide-based active materials using the electrode formulations described herein. In some embodiments, it may be desirable to extend the cycling life of negative electrodes that include a combination of graphitic carbon and silicon-based active materials with an acceptable reduction in specific capacity, and the superior cycling performance herein is achieved using such active material blends.

[0024] To achieve the results described herein, the negative electrode includes several improvements in design that can be considered individually or in combination to provide improved cycling performance, and for at least some embodiments, a combination of certain electrode features can provide surprising synergistic performance improvements in terms of longer cycling stability. The electrolytes described herein further exploit these electrode improvements. In particular, the negative electrode can be designed with a composite binder that has high tensile strength while introducing some elongation capability. Nanoscale conductive carbons such as carbon nanotubes, carbon black, carbon nanofibers, or combinations thereof as conductive electrode additives have been found to improve cycling of negative electrodes with silicon-based active materials. These features can be combined with electrode loading and density design that provides good energy density-based performance for the resulting consumer electronics cell design. Cycling can be further improved by adding complementary lithium to the cell and / or balancing the active materials in each electrode.

[0025] The graphite component of the active material blend in the negative electrode can provide electrical conductivity. However, it has been found that an appropriate amount of nanoscale carbon can further stabilize the negative electrode with respect to cycling. The nanoscale carbon can take the form of carbon nanotubes, carbon nanofibers, or carbon nanoparticles, such as carbon black. The usefulness of nanoscale conductive carbon for the cycling stability of silicon-based negative electrodes has been previously discovered as described in U.S. Pat. No. 9,190,694 B2 to Lopez et al., entitled "High Capacity Anode Materials for Lithium Ion Batteries," and U.S. Pat. No. 9,780,358 B2 to Masarapu et al., entitled "Battery Designs With High Capacity Anode Materials and Cathode Materials," both of which are incorporated herein by reference. In general, the electrode contains at least about 1 wt. % nanoscale conductive carbon to achieve stable cycling.

[0026] In lithium-ion cells, the lithium reactive for cycling is generally provided in the positive electrode active material, which migrates to the negative electrode during the initial charge of the cell, where it is then available for discharging the cell. Silicon-based negative electrodes can generally exhibit large irreversible capacity loss during the first charge of the cell. The capacity loss can generally be associated with the corresponding irreversible changes to the material during the initial charge of the cell. For example, a solid electrolyte interphase (SEI) layer forms in association with the negative electrode active material as a result of reaction with the typical electrolyte used in the cell. If a stable SEI layer is formed, it can stabilize the cell during cycling. Presumably, other irreversible changes also occur with respect to the silicon-based active composition. The irreversible capacity loss of the first cycle is generally significantly larger than any capacity loss per cycle associated with subsequent cycling of the cell, but the second, third and some additional cycles can still experience large capacity loss per cycle due to carryover of initial changes to the first few cycles, rather than being fully reached in the first cycle. A relatively large irreversible capacity loss (IRCL) can also reduce the cycling capacity and the energy and power output of the cell during cycling. Larger format cells can have increased capacity at fewer cycles, with practical effects that can be, for example, improved permeation of electrolyte through the electrode stack.

[0027] To reduce the loss of energy and power output of the cell as a result of irreversible capacity loss, complementary lithium can be introduced to provide additional lithium to the cell. The introduction of complementary lithium can reduce the introduction of cathode active material that does not cycle due to the loss of active lithium capacity associated with IRCL. Complementary lithium refers to active lithium introduced directly or indirectly into the cell that is separate from the positive electrode active material to replace lost lithium in the irreversible process and provide other beneficial effects. Applicant has discovered that complementary lithium provided in an amount greater than that corresponding to the replacement of irreversible capacity loss can further stabilize cycling. For lithium-rich + manganese-rich nickel manganese cobalt oxide, positive electrode active material, this cycling stabilization is described in U.S. Patent No. 9,166,222 to Amiruddin et al. (hereinafter the '222 patent), entitled "Lithium Ion Batteries With Supplemental Lithium," which is incorporated herein by reference.

[0028] Various approaches to introduce complementary lithium can be used, including, for example, adding a lithium active material (e.g., lithium metal powder or foil) to the negative electrode, adding a sacrificial lithium source to the positive electrode, incorporating a sacrificial lithium electrode into the cell structure, electrochemically prelithiating the negative electrode, etc. These approaches are described in more detail in the '222 patent and U.S. Pat. No. 9,190,694 to Lopez et al., entitled "High Capacity Anode Materials for Lithium Ion Batteries" (hereinafter the '694 patent), both of which are incorporated herein by reference. It has also been found that in some embodiments, electrochemical approaches such as those described in PCT Publication WO 2013 / 082330 to Grant et al., entitled "Method for Alkylating Anodes," which is incorporated herein by reference, may be advantageous. In general, the complementary lithium can be introduced in an amount that compensates for a portion of the irreversible capacity loss, nearly all of the irreversible capacity loss, or more than the irreversible capacity loss, but generally is 30% or less than the capacity of the negative electrode active material. In some embodiments, the complementary lithium can compensate for about 90% to about 200% of the first cycle irreversible capacity loss of the anode.

[0029] Previous work by the applicant has found that the use of a high tensile strength polymer binder, which can be met by a suitable polyimide, significantly facilitates cycling of silicon-based anodes. In particular, the tensile strength of the polymer binder can be at least about 60 MPa. To further extend cycling stability, it has been discovered that a polymer binder blend can provide further improved cycling performance. One component of the polymer binder blend can be a high tensile strength polymer, such as a polyimide, and the second polymer can have a lower Young's modulus (elastic modulus) value to provide a more elastic polymer, such as polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, lithiated polyacrylic acid, or mixtures thereof. While providing tensile strength, the polymer binder should also provide good adhesion so that the electrode remains laminated to the current collector. A desired blend can include at least about 50% by weight of a high tensile strength polymer and at least about 5% by weight of a polymer binder having a Young's modulus of about 2.4 GPa or less and an elongation of at least about 35% for some embodiments.

[0030] Anode design generally involves a balance of factors to achieve target capacity while providing reasonable cycling. The incorporation of the desired electrolyte herein significantly further extends cycling stability. As seen in the results of the following examples, batteries using silicon-based anode active materials have been able to cycle for over 750 cycles while maintaining over 80% of cell capacity. At the same time, practical anode designs can achieve good cycling and high energy density when combined with appropriate cathode designs. Electrode designs are described in detail below. Also described are the balance of design features to achieve these results.

[0031] In general, the electrode designs described herein can be adapted to cylindrical cells or more rectangular or prismatic batteries. Cylindrical batteries generally have a wound electrode structure, while prismatic batteries can be wound or stacked electrodes. In general, to achieve the desired performance capacity with the appropriate electrode design in terms of electrode loading and density, a cell can include multiple electrodes of each polarity that can be stacked together with separator materials between the electrodes of the cell. Winding the electrodes can provide a similar effect with appropriate internal resistance due to electronic conductivity and ionic mobility, as well as good packing of the electrodes in a suitable container. The size of the battery generally affects the total capacity and energy output of the cell. The designs described herein are based on obtaining the desired high energy density while providing the desired cycling of the cell based on silicon-based active materials.

[0032] The discovery of the improved electrolyte formulation resulted in a significant extension of cycling stability. In particular, cells having a significant fraction of silicon-based active material were cycled for at least 800 cycles without capacity degradation to values ​​less than 80% of the third cycle capacity at a discharge rate of C. The resulting cycling stability is suitable for use in electric vehicle and similar high capacity applications.

[0033] General battery characteristics The negative and positive electrode structures can be assembled into a suitable cell. As further described below, the electrodes are generally formed in association with current collectors to form an electrode structure. A separator is placed between the positive and negative electrodes to form a cell. The separator is electrically insulating while providing at least selected ionic conductivity between the two electrodes. A variety of materials can be used as the separator. Some commercially available separator materials can be formed from polymers such as polyethylene and / or polypropylene, which are porous sheets that provide ionic conductivity. Commercially available polymer separators include, for example, the Celgard® line of separator materials from Asahi Kasei (Japan). Ceramic-polymer composite materials have also been developed for the separator. These ceramic composite separators can be stable at high temperatures, and the composite materials can reduce fire risks. Polymer-ceramic composites for lithium ion battery separators are sold under the tradenames Separion® by Evonik Industries, Germany and Lielsort® by Tiejin Lielsort Korea Co., Ltd. It is also possible to form the separator using a porous polymer sheet coated with a gel-forming polymer. Such separator designs are further described in U.S. Pat. No. 7,794,511 B2 to Wensley et al., entitled "Battery Separator for Lithium Polymer Battery," which is incorporated herein by reference. Suitable gel-forming polymers include, for example, polyvinylidene fluoride (pvdf), polyurethane, polyethylene oxide (PEO), polypropylene oxide (PPO), polyacylonitrile, gelatin, polyacrylamide, polymethyl acrylate, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, polytetraethylene glycol diacrylate, copolymers thereof, and mixtures thereof.

[0034] The electrolyte provides ion transport between the anode and cathode of the battery during the charging and discharging processes. Electrolytes for lithium-ion batteries incorporate a non-aqueous solvent and a lithium salt. Improved electrolytes for silicon-based electrodes are described in detail below. The electrolyte is generally permeated into the cell before sealing the case.

[0035] The electrodes described herein can be assembled into various commercially available cell / battery designs, such as prismatic batteries, wound cylindrical cells, coin cells, or other suitable cell / battery designs. A cell can include a single electrode pair or multiple electrode pairs assembled in parallel and / or series electrical connection. The electrode stack can have additional electrodes such that the stack ends with the same polarity as the other end of the stack for convenient placement in a container. Although the electrode structures described herein can be used in batteries for primary or single charging, the resulting batteries generally have the desired cycling characteristics for secondary battery applications over multiple cycling of the battery.

[0036] In some embodiments, the positive and negative electrodes can be stacked with a separator between them, and the resulting stack structure can be rolled into a cylindrical or prismatic configuration to form a cell structure. Appropriate conductive tabs can be welded to the current collectors, etc., and the resulting jellyroll structure can be placed into a metal canister or polymer package with the negative and positive tabs welded to appropriate external contacts. Electrolyte is added to the canister, and the canister is sealed to complete the cell. Some currently used rechargeable commercially available cells include, for example, cylindrical 18650 cells (diameter 18 mm and length 65 mm), 26700 cells (diameter 26 mm and length 70 mm), although other cell / battery sizes as well as selected size prismatic cells and foil pouch cells / batteries can be used.

[0037] Pouch batteries can be particularly desirable for a variety of applications, including certain vehicle applications, due to their stacking convenience and relatively low container weight. Pouch battery designs for vehicle batteries incorporating high capacity cathode active materials are further described in U.S. Patent No. 8,187,752 to Buckley et al., entitled "High Energy Lithium Ion Secondary Batteries," and U.S. Patent No. 9,083,062 B2 to Kumar et al., entitled "Battery Packs for Vehicles and High Capacity Pouch Secondary Batteries for Incorporation into Compact Battery Packs," both of which are incorporated herein by reference. Although the pouch battery design is particularly convenient for use in certain battery pack designs, pouch batteries can also be used effectively in other situations.

[0038] 1-4 show a representative embodiment of a pouch battery. In this embodiment, the pouch battery 100 includes a pouch enclosure 102, an electrode core 104, and a pouch cover 106. The electrode core is further described below. The pouch enclosure 102 includes a cavity 110 and an edge 112 surrounding the cavity. The cavity 110 has dimensions such that the electrode core 104 can fit within the cavity 110. As shown in FIGS. 2 and 3, the pouch cover 106 can be sealed around the edge 112 to seal the electrode core 104 within the sealed battery. End tabs 114, 116 extend outwardly from the sealed pouch for electrical contact with the electrode core 104. FIG. 3 is a schematic cross-sectional view of the battery of FIG. 2 as viewed along line 3-3. With various configurations of edges and seals, many additional embodiments of the pouch battery are possible.

[0039] FIG. 4 illustrates an embodiment of an electrode core 104 that generally includes an electrode stack. In this embodiment, the electrode stack 130 includes anode structures 132, 134, 136, cathode structures 138, 140, and separators 150, 152, 154, 156 disposed between adjacent cathodes and anodes. The separators may be provided as a single folded sheet with the electrode structures disposed within the pleats of the separator. The anode structures 132, 134, 136 include anodes 160, 162, anodes 164, 166, and anodes 168, 170 disposed on either side of current collectors 172, 174, 176, respectively. The cathode structures 138, 140 include cathodes 180, 182, anodes 184, 186, respectively disposed on opposite sides of current collectors 188, 190, respectively. Tabs 192, 194, 196, 198, 200 are connected to current collectors 172, 188, 174, 190, 176, respectively, to facilitate connection of the individual electrodes in series or parallel. For vehicle applications, the tabs are typically connected in parallel, with tabs 192, 196, 200 electrically connected to electrical contacts accessible from outside the container, and tabs 194, 198 electrically connected to electrical contacts as opposite poles accessible from outside the container.

[0040] The electrode stack can have an additional negative electrode such that both outer electrodes adjacent the container are negative. Typically, a battery with stacked electrodes of the dimensions described herein will have 5 to 40 negative electrode elements (current collectors coated on both sides with active material), and in further embodiments, 7 to 35 negative electrode elements. The corresponding number of positive electrode elements will generally be one less than the negative electrode elements. A person of ordinary skill in the art will recognize that additional ranges of electrode numbers within the explicit ranges above are contemplated and are within the present disclosure.

[0041] As mentioned above, the wound electrodes can be used for either cylindrical batteries or generally prismatic batteries. Wound cells for cylindrical lithium ion batteries are further described in U.S. Patent No. 8,277,969 to Kobayashi et al., entitled "Lithium Ion Secondary Battery," which is incorporated herein by reference. Prismatic batteries with wound electrodes are described in U.S. Patent No. 7,700,221 to Yeo, entitled "Electrode Assembly and Lithium Ion Secondary Battery Using the Same," which is incorporated herein by reference (the '221 patent). Kobayashi's '969 patent and Yeo's '221 patent do not describe how to achieve adequate cycling or high energy density with silicon-based active materials. Designs for prismatic batteries using wound electrodes are further described, for example, in the '221 patent. The specific design of either the stacked combination of electrodes or the wound cell may also be influenced by the target size and target capacity of the battery.

[0042] The improved anode can be used for various applications and cell / battery designs. For electrode stacks, the area of ​​the electrodes can be appropriately selected based on the volume and design constraints for a particular application. The following discussion focuses on large cells that are typically designed for vehicle applications, such as drones, cars, trucks, or other vehicles. However, the improved anode described herein can be effectively used for consumer electronics applications that can be based on smaller cell configurations. It should also be noted that automobiles can use smaller consumer electronics cells, and Tesla cars are currently known to use thousands of small consumer electronics cells in their battery packs. In general, within a certain range, larger cells / batteries can achieve greater energy density. It may be desirable to select a positive electrode active material based on a particular application to balance various considerations, such as energy density.

[0043] Selection of electrode parameters allows the design of high gravimetric energy density cells to incorporate a balance of factors such as electrode area, number of electrode structures, and battery capacity. Electrode area refers to the spatial extent of one electrode along one side of a current collector. FIG. 1 shows the length "L" and FIG. 3 shows the width "W" of the electrode. As shown in the figures, the area of ​​the electrode can be defined as L×W. In some embodiments, the area of ​​each electrode can be similar such that the dimensions of a battery including an electrode stack can have a length and width similar to the length and width of each electrode in the stack. In some embodiments, the separator can be in the form of a sheet with an area slightly larger than the area of ​​the electrodes, and in some embodiments, the separator can be folded, pleated, or formed with pockets, with the electrodes placed in the pleats or pockets of the separator.

[0044] electrolyte We refer to solutions containing solvated ions as electrolytes, and ionic compositions that dissolve to form solvated ions in a suitable liquid as electrolyte salts. Electrolytes for lithium-ion batteries can include one or more selected lithium salts, non-aqueous solvents, and optional additives. The desired electrolytes described herein that achieve unprecedented cycling have appropriately selected solvents and avoid components that have been found to specifically degrade cycling performance.

[0045] Suitable lithium salts generally have an inert anion. Suitable lithium salts include, for example, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonylimide), lithium trifluoromethanesulfonate, lithium tris(trifluoromethylsulfonyl)methide, lithium tetrafluoroborate, lithium perchlorate, lithium tetrachloroaluminate, lithium chloride, lithium difluorooxalatoborate, and combinations thereof. Of particular interest are lithium hexafluorophosphate and lithium tetrafluoroborate. In some embodiments, the electrolyte comprises a 1M to 2M concentration of lithium salt, in further embodiments from about 1.1M to about 1.9M, and in other embodiments from about 1.25M to about 1.8M of lithium salt. A person of ordinary skill in the art will recognize that additional ranges of electrolyte salt concentrations within the explicit ranges above are contemplated and are within the present disclosure.

[0046] For lithium ion batteries of interest, non-aqueous liquids are generally used to dissolve the lithium salt in the non-aqueous solvent. The solvent generally does not dissolve the electrically active material. For the electrolytes described herein to provide surprisingly improved cycling performance, the choice of solvent is important. Generally, the solvent comprises about 5% to about 30% by weight of fluoroethylene carbonate (FEC), in further embodiments about 7% to about 27% by weight, and in additional embodiments about 8% to about 25% by weight of FEC. Correspondingly, the solvent is generally substantially free of ethylene carbonate, since ethylene carbonate has been found to be detrimental with respect to cycling. Ethylene carbonate has a melting point of about 35° C. and is solid at room temperature. Fluoroethylene carbonate melts at about room temperature, 18 to 23° C. Also, electrolytes with fluoroethylene carbonate have been found to have excellent low temperature performance, as described in the above-mentioned '147 application.

[0047] The electrolyte solvent generally also includes room temperature liquid components, and solvents of particular interest further include linear carbonate esters and optional additives. Desirable linear carbonate esters include, for example, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate. In some embodiments, the total volume of dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate added to the solvent is a total contribution from dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate of about 50% to about 95% by volume, further embodiments about 55% to about 92.5% by volume, and additional embodiments about 60% to about 91% by volume. In some embodiments, the solvent consists essentially of fluoroethylene carbonate and one or more of dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate. A person of ordinary skill in the art will recognize that additional ranges of solvent components within the explicit ranges above are contemplated and are within the scope of the present disclosure.

[0048] In some embodiments, the solvent can further include propylene carbonate and / or fluorobenzene. When one or both of these optional solvent components are present, the solvent can generally include from about 0.5% to about 12% by volume, in further embodiments from about 0.75% to about 10% by volume, and in other embodiments from about 1% to about 8% by volume of one or both of these solvent components. Although the PC or FB solvent components do not significantly alter cycling performance, these solvent components may be desirable due to processing advantages such as reduced gas formation. A person of ordinary skill in the art will recognize that additional ranges of PC and / or FB solvent concentrations within the explicit ranges above are contemplated and are within the present disclosure.

[0049] Generally, the solvent may contain other minor components, generally at about 20% by volume or less, in some embodiments about 10% by volume or less, in other embodiments about 0.01% to about 5% by volume, and in further embodiments about 0.1% to about 1% by volume of the total of these other solvent components. A person of ordinary skill in the art will recognize that additional ranges of solvent components within the explicit ranges above are contemplated and are within the scope of the present disclosure. In some embodiments, other suitable solvent components that may optionally be present in minor amounts include, for example, 2-methyltetrahydrofuran, dioxolane, tetrahydrofuran, γ-butyrolactone, dimethylsulfoxide, acetonitrile, formamide, dimethylformamide, triglyme (tri(ethylene glycol) dimethyl ether), diglyme (diethylene glycol dimethyl ether), DME (glyme or 1,2-dimethyloxyethane or ethylene glycol dimethyl ether), nitromethane, and mixtures thereof. Other trace fluorinated solvent components can include, for example, fluorinated vinyl carbonate, monochloroethylene carbonate, monobromoethylene carbonate, 4-(2,2,3,3-tetrafluoropropoxymethyl)-[1,3]dioxolan-2-one, 4-(2,3,3,3-tetrafluoro-2-trifluoromethylpropyl)-[1,3]dioxolan-2-one, 4-trifluoromethyl-1,3-dioxolan-2-one, bis(2,2,3,3-tetrafluoro-propyl)carbonate, bis(2,2,3,3,3-pentafluoro-propyl)carbonate, or mixtures thereof. Additional fluorinated trace solvent components include fluorinated ethers described, for example, in U.S. Patent Application Publication No. 2018 / 0062206 to Li et al., entitled "Fluorinated Ether as Electrolyte Co-Solvent for Lithium Metal Based Anode," and WO 2018 / 051675 to Takuya et al., entitled "Lithium Secondary Battery," both of which are incorporated by reference herein.

[0050] Common solvent compounds that are generally considered to be desirable solvent components for lithium-ion cells have been found to be detrimental to cycling with the improved electrodes described herein. In particular, ethylene carbonate is generally excluded from the electrolytes described herein. Thus, the electrolytes generally contain no more than 0.1% by volume of ethylene carbonate.

[0051] Electrode structure The electrodes of the cell include active materials along with binders and conductive additives. The electrodes are formed into sheets, dried, and pressed to achieve the desired density and porosity. Typically, the electrode sheets are formed directly on a metal current collector, such as a metal foil or a thin metal grid. In many cell structures, electrode layers are formed on both sides of the current collector to provide the desired performance in the assembled cell or battery. The electrode layers on both sides of the current collector are at the same potential in the cell and can be considered elements of the same electrode structure, but the current collector itself, although part of the electrode structure, is generally not considered part of the electrode because it is electrochemically inactive. Thus, references to the physical aspects of the electrode generally refer to the electrode composition of one layer within the electrode structure. The conductive current collector can facilitate the flow of electrons between the electrode and an external circuit.

[0052] In some embodiments, when the positive or negative electrode uses a high loading level, the density of the electrode can be reduced to provide good cycling stability of the electrode. The density of the electrode is a function of the pressing pressure within a suitable range. In general, the density of the electrode cannot be arbitrarily increased without sacrificing performance with respect to the loading level while achieving the desired cycling performance and capacity at higher discharge rates. In the following sections, the characteristics of certain negative and positive electrode layers are described.

[0053] In some embodiments, the current collector can be formed from nickel, aluminum, stainless steel, copper, etc. The electrode material can be cast onto the current collector as a thin film. The electrode material together with the current collector can then be dried, for example in an oven, to remove the solvent from the electrode. In some embodiments, the dried electrode material can be subjected to a pressure of about 2 to about 10 kg / cm2 while in contact with a current collector foil or other structure. 2 (kilograms per square centimeter) pressure. The current collector used in the positive electrode can have a thickness of about 5 microns to about 30 microns, in other embodiments about 10 microns to about 25 microns, and in further embodiments about 14 microns to about 20 microns. In one embodiment, the positive electrode uses an aluminum foil current collector. The current collector used in the negative electrode can have a thickness of about 2 microns to about 20 microns, in other embodiments about 4 microns to about 14 microns, and in further embodiments about 6 microns to about 10 microns. In one embodiment, the negative electrode uses a copper foil as a current collector. A person of ordinary skill in the art will recognize that additional ranges of current collector thickness within the explicit ranges above are contemplated and are within the present disclosure.

[0054] negative electrode The basic electrode design includes a blend of active composition, polymer binder and conductive diluent. As mentioned above, in some embodiments, the improved electrode design may include a polymer binder blend and a blend of active composition and a nanoscale conductive carbon additive. The active material blend may include, in some embodiments, a silicon-based active material such as a majority of silicon oxide composite and at least 10 wt.% of separate graphite. It has also been discovered that stabilization of electrode cycling with silicon-based active material can be obtained by blending polyimide to provide high mechanical strength with a more deformable polymer portion that still provides good electrode performance in a synergistic binder blend. Although graphite can provide electrical conductivity to the electrode, nevertheless, in some embodiments, the amount of separate nanoscale conductive carbon can be significant to the ability to fabricate long-term cycling anodes. In general, graphite is electrochemically active, but nanoscale conductive carbon is not considered to be electrochemically active. These improved design aspects are therefore incorporated into the electrode along with further previously discovered silicon-based electrode improvements.

[0055] There is great interest in high capacity anode active materials based on silicon. Silicon-based active materials have generally not achieved cycling stability suitable for automotive applications of batteries containing significant amounts of silicon. The '535 application demonstrates suitable cycling success for consumer electronics applications and the like, with cycling up to about 200-300 cycles at values ​​of at least 80% of initial capacity. Applicant has achieved particular success with cycling stability using materials based primarily on silicon oxide composites. Provided herein are electrodes that can be successfully cycled for more than 600 cycles without capacity dropping below 80% by cycling over a large voltage range at a suitable rate. Thus, the present work is directed to extending cycling stability into the region suitable for automotive applications.

[0056] As described herein, the active composition blended with silicon-based active material and graphitic carbon provides improved cycling results. In general, the total capacity of the negative electrode blended active material can be at least about 750 mAh / g, in further embodiments at least about 900 mAh / g, in additional embodiments at least about 1000 mAh / g, and in other embodiments at least about 1100 mAh / g, cycled at a rate of C / 3 from 5 millivolts (mV) to 1.5 V against lithium metal. The blended active material can include at least about 40% by weight of silicon-based active material, in further embodiments at least about 50% by weight of silicon-based active material, in other embodiments from about 55% by weight to about 95% by weight of silicon-based active material, and in additional embodiments from about 60% by weight to about 90% by weight of silicon-based active material. Correspondingly, the blended active material can include from about 5% graphite to about 65% graphite, in further embodiments from about 7% graphite to about 60% graphite, in additional embodiments from about 8% graphite to about 55% graphite, and in other embodiments from about 10% graphite to about 50% graphite. A person of ordinary skill in the art will recognize that additional ranges of specific discharge capacity and concentrations of silicon-based active materials within the explicit ranges above are contemplated and are within the present disclosure.

[0057] As described above and in detail below, suitable silicon-based active materials may include composites with carbon components. The silicon-based active materials are described in detail in the following sections. Composites refer to particulate materials with components intimately combined in a monolithic material with effective uniformity on a suitable scale, as opposed to blends, which include mixtures held together by polymer binders. Composite components may include, for example, silicon, oxygen, carbon, and the like. Without wishing to be limited by theory, the carbon components of composites with silicon are generally not believed to be electrochemically active, and are generally not graphite-based. However, activity is an abstract concept given the intimate combinations in the composite and crystal structure can be very complex and difficult to evaluate. In any case, the carbon components of the composite are readily understood by those skilled in the art as being distinguishable from the separate graphite, which is not present in the composite in the active material blend. The following examples are based on commercially available composite compositions believed to contain primarily silicon suboxide and some amount of elemental silicon crystals and elemental carbon in the combined composite particulate materials.

[0058] Graphite is commercially available in natural and synthetic forms, and suitable graphites include natural or synthetic graphite. Graphite is a crystalline form of carbon, containing carbon covalently bonded in sheets. As used herein, graphite refers to graphitic carbon without requiring perfect crystallinity, and some natural graphitic materials may contain some crystalline impurities. However, graphite generally refers to materials dominated by the graphitic structure as recognized in the art. Graphite is conductive along the plane of the covalently bonded carbon sheets stacked in the crystal. Graphite forms of crystalline carbon are capable of intercalating lithium, and are therefore an established electrochemically active material for lithium-ion batteries.

[0059] The graphite particles can have an average particle size of about 1 micron to about 30 microns, in further embodiments about 1.5 microns to about 25 microns, and in other embodiments about 2 microns to about 20 microns. In general, it is believed desirable for the graphite to not contain particles larger than the thickness of the electrode to avoid an uneven electrode surface, and graphite particles having a size significantly smaller than 1 micron may have reduced crystallinity. In some embodiments, the graphitic carbon can have a D50 (mass median diameter) of about 5 microns to about 50 microns, in further embodiments about 7 microns to about 45 microns, and in additional embodiments about 10 microns to about 8 microns to about 40 microns. Also, in some embodiments, the BET surface area of ​​the graphitic carbon active material (assessable according to ISO 4652) is about 1 m 2 / g~about 100m 2 / g, and in a further embodiment, about 5m 2 / g~about 85m 2 / g and in a further embodiment, about 7.5 m 2 / g~about 60m 2 / g. A person of ordinary skill in the art will recognize that additional ranges of particle size and surface area for the graphitic carbon active material are contemplated and are within the present disclosure. In contrast, conductive carbon blacks and the like (called quasicrystalline) generally have particle sizes of about 40 m 2 / g~1000m 2 / g or more.

[0060] With respect to the polymer binder, applicants have obtained suitable cycling of silicon-based cells using high tensile strength binders, such as polyimide binders. See U.S. Pat. No. 9,601,228 to Deng et al., entitled "Silicon Oxide Based High Capacity Anode Materials for Lithium Ion Batteries," (hereinafter the '228 patent), which is incorporated herein by reference. In some embodiments to obtain longer cycling stability, it has surprisingly been found that polymer binder blends further stabilize cycling. In particular, a second polymer or combination of polymers providing a lower modulus of elasticity (corresponding to higher elasticity) can be blended with the high tensile strength polyimide. The binder blend generally comprises at least about 50% by weight polyimide, in further embodiments at least about 55% by weight polyimide, and in other embodiments from about 60% to about 95% by weight polyimide. Similarly, the binder blend generally comprises at least about 5% by weight of a polymer having a low modulus, and in further embodiments at least about 10% by weight, and in other embodiments from about 12% to about 40% by weight of a polymer having a low modulus, as further defined below. A person of ordinary skill in the art will recognize that additional ranges of amounts of polymer within the explicit ranges above are contemplated and are within the present disclosure. The polymers of the blend can be selected to be soluble in the same solvent.

[0061] Polyimides are polymers based on repeating units of imide monomer structures. Polyimide polymer chains can be aliphatic, but for high tensile strength applications, the polymer backbone is generally aromatic, with the polymer backbone extending along the N atoms of the polyimide structure. For silicon-based anodes that exhibit significant morphology changes during cycling, it has been found that thermosetting polyimide polymers are desirable for high capacity anodes. This may be due to their high mechanical strength. The following table lists sources of high tensile strength polyimide polymers and the corresponding polyimide polymer names.

[0062] JPEG2025060873000002.jpg65169

[0063] The polyimide polymer can have a tensile strength of at least about 60 MPa, in further embodiments at least about 100 MPa, and in other embodiments at least about 125 MPa. Some commercially available polyimides with high tensile strength can also have relatively high elongation values. Elongation value is the amount of elongation that a polymer can withstand before tearing. In some embodiments, the polyimide can have an elongation of at least about 40%, in further embodiments at least about 50%, and in other embodiments at least about 55%. Tensile strength and elongation values ​​can be measured according to the procedures of ASTM D638-10 Standard Test Method for Tensile Properties of Plastics or ASTM D882-91 Standard Test Method for Tensile Properties of Thin Plastic Sheets, both of which are incorporated herein by reference. Based on values ​​reported by commercial suppliers, the results from these alternative ASTM protocols appear to be similar to one another for polyimides. A person of ordinary skill in the art will recognize that additional ranges of polymer properties within the explicit ranges above are contemplated and are within the present disclosure.

[0064] A suitable more flexible polymer component can be selected that is inert to the electrochemistry of the cell and compatible with processing with polyimide. Particularly suitable more flexible polymer components include, for example, polyvinylidene fluoride (PVdF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), lithiated polyacrylic acid (LiPAA) or mixtures thereof. Regarding polymer properties, some significant properties for high capacity anode applications are summarized in the following table.

[0065] JPEG2025060873000003.jpg66169

[0066] PVDF means polyvinylidene fluoride, CMC means sodium carboxymethyl cellulose, SBR means styrene-butadiene rubber, and LiPAA means lithiated polyacrylic acid. PVDF, CMC, and SBR are commercially available from a number of sources. LiPAA can be produced from LiOH and commercially available polyacrylic acid (PAA). For example, a stoichiometric amount of LiOH can be added to a solution of PAA, with one mole of LiOH per monomer unit of PAA. The formation and use of LiPAA is further described in Li et al., “Lithium polyacrylate as a binder for tin-cobalt-carbon negative electrodes in lithium-ion batteries”, Electrochemica Acta 55 (2010) 2991-2995, which is incorporated herein by reference.

[0067] By elongation is meant the percentage of elongation before the polymer is torn. In general, to accommodate silicon-based materials, an elongation of at least about 30%, in some embodiments at least about 50% and in further embodiments at least about 70% is desired. For polymer binder blends, it may be desirable for the more elastic polymer binder component to have an elastic modulus (alternatively referred to as Young's modulus or tensile modulus) of about 2.4 GPa or less, in further embodiments at about 2.25 GPa or less, in other embodiments at about 2 GPa or less, and in additional embodiments at about 1.8 GPa or less. Those skilled in the art will recognize that additional ranges of properties of the more elastic polymer component within the explicit ranges above are contemplated and are within the present disclosure.

[0068] To form the electrode, the powder can be blended with the polymer in a suitable liquid, such as a solvent for dissolving the polymer. Polyimides and PVdF can generally be processed in N-methylpyrrolidone (NMP), although other suitable organic solvents can be used. Aqueous processable polyimides are commercially available and are suitable for blending with a wide range of other polymers. The particulate components of the electrode, i.e., the active material and nanoscale conductive carbon, can be blended with the polymer binder blend in a solvent before forming a paste. The resulting paste can be pressed into an electrode structure.

[0069] Higher active material loadings of the binder are possible. In some embodiments, the negative electrode has about 75 to about 92 weight percent negative electrode active material, in other embodiments about 77 to about 90 weight percent negative electrode active material, and in further embodiments about 78 to about 88 weight percent negative electrode active material. In some embodiments, the negative electrode has about 6 to about 20 weight percent polymer binder, in other embodiments about 7 to 19 weight percent polymer binder, and in further embodiments about 8 to 18 weight percent polymer binder. Also, in some embodiments, the negative electrode includes about 1 to about 7 weight percent nanoscale conductive carbon, in further embodiments about 1.5 to about 6.5 weight percent, and in additional embodiments about 2 to about 6 weight percent nanoscale conductive carbon. A person of ordinary skill in the art will recognize that additional ranges of polymer loadings within the explicit ranges above are contemplated and are within the present disclosure.

[0070] For improved cycling of the negative electrode, nanoscale carbon additives or combinations thereof have been found to be particularly desirable. Nanoscale conductive carbon generally refers to particles of elemental carbon with high surface area, with at least two dimensions of the primary particle being submicron. Suitable nanoscale conductive carbons include, for example, carbon black, carbon nanotubes, and carbon nanofibers. In some embodiments, the nanoscale conductive carbon additive used in the negative electrode can include carbon nanotubes, carbon nanofibers, carbon nanoparticles (e.g., carbon black), or combinations thereof. In some embodiments, to achieve improved performance, the conductive additive can have a conductivity of at least about 40 S / cm, in some embodiments at least about 50 S / cm, and in further embodiments at least about 60 S / cm. One of ordinary skill in the art will recognize that additional ranges of particle loading and conductivity within the explicit ranges above are contemplated and are within the present disclosure.

[0071] The electrical conductivity, which is the reciprocal of the resistance, may be reported by the vendor, and the electrical conductivity is generally measured using a specific technique developed by the vendor. For example, the measurement of the electrical resistance of carbon black is performed between two copper electrodes using Super P™ carbon black. See Imerys Graphite&Carbon, A Synopsis of Analytical Procedures, 2019 (http: / / www.imerys-graphite-and-carbon.com / wordpress / wp-app / uploads / 2019 / 02 / Analytical-Procedures Web 21Feb19.pdf). Also, appropriate complementary conductive additives can be added to provide longer cycling stability. Also, some suppliers list the conductive carbon concentration to achieve the conductive percolation threshold.

[0072] Carbon black means a synthetic carbon material and may alternatively be referred to as acetylene black, furnace black, thermal black or other names that suggest a synthetic approach. Carbon black is generally described as amorphous carbon, although in at least some forms of carbon black there is a suggestion of small domains of short or medium range that correspond to graphite or diamond crystal structures. However, for practical purposes the material can be considered to be amorphous. Based on ISO Technical Specification 80004-1 (2010), carbon black is a nanostructured material. Although the primary particles of carbon black can range up to tens of nanometers, the primary particles are generally rigidly fused into chains or other aggregates, and the smallest dispersed units can be considered to be about 80 nm to 800 nm, which is still submicron. Carbon blacks synthesized to provide the desired level of electrical conductivity are commercially available, such as Super-P® (Imerys), Ketjenblack® (Akzo Nobel), Shawinigan Black® (Chevron-Phillips), and Black Pearls 2000® (Cabot).

[0073] Carbon nanofibers are high aspect ratio fibers that generally contain graphene layers in the form of plates, cones, or other shapes, while carbon nanotubes contain graphene sheets folded into tubes. Carbon nanofibers have diameters of 250 nm or less and are commercially available, for example, from Pyrograf® carbon nanofibers (Pyrograf Products, Inc.) or American Elements, Inc. Carbon nanotubes have been found to be desirable conductive additives that can improve the cycling performance of either positive or negative electrodes. Single-wall or multi-wall carbon nanotubes are also available from American Elements, Inc. (CA, USA), Cnano Technologies (China), Fuji, Inc. (Japan), Alfa Aesar (MA, USA), or NanoLabs (MA, USA).

[0074] The negative electrodes used in the cells described herein can have high active material loading levels with appropriately high electrode density. For a particular active material loading level, density is inversely proportional to thickness, so that an electrode with a higher density will be thinner than an electrode with a lower density. The loading is equal to density multiplied by thickness. In some embodiments, the battery negative electrode has a density of at least about 1.5 mg / cm 2 and in other embodiments, about 2 mg / cm 2 ~about 8mg / cm 2 and about 2.5 mg / cm in additional embodiments. 2 ~about 6mg / cm 2 and about 3 mg / cm in other embodiments. 2 ~about 4.5mg / cm 2 In some embodiments, the negative electrode of the battery has a negative electrode active material loading level of about 0.5 g / cc (cc=cubic centimeter (cm 3In yet another embodiment, the silicon oxide-based electrode has an active material density of from about 0.6 g / cc to about 1.5 g / cc, and in additional embodiments from about 0.7 g / cc to about 1.3 g / cc. Similarly, the silicon oxide-based electrode can have an average dry thickness of at least about 15 microns, and in further embodiments at least about 20 microns, and in additional embodiments from about 25 microns to about 75 microns. The resulting silicon oxide-based electrode has an active material density of at least about 3.5 mAh / cm 2 and in further embodiments at least about 4.5 mAh / cm 2 , and in additional embodiments at least about 6 mAh / cm 2 A person of ordinary skill in the art will recognize that additional ranges of active material loading levels and electrode densities within the explicit ranges above are contemplated and are within the present disclosure.

[0075] High capacity silicon-based anode materials Generally, the battery design herein is based on a high capacity anode active material. Specifically, the anode active material generally has a specific capacity of at least about 800 mAh / g, in further embodiments at least about 900 mAh / g, in additional embodiments at least about 1000 mAh / g, in some embodiments at least about 1150 mAh / g, and in other embodiments at least about 1400 mAh / g when cycled at a rate of C / 10 against lithium metal at 0.005V to 1.5V. Thus, the specific capacity of the negative electrode active material can be evaluated in a cell with a lithium metal counter electrode. However, in the batteries described herein, the negative electrode can exhibit a reasonably comparable specific capacity when cycled against a high capacity lithium metal oxide positive electrode active material. In batteries using non-lithium metal electrodes, the specific capacity of each electrode can be evaluated by dividing the battery capacity by the weight of each of the active materials. As described herein, by combining silicon-based active materials and graphitic carbon active materials, good capacity is observed and desirable cycling results can be obtained.

[0076] Elemental silicon, silicon alloys, silicon composites, etc. can have a low potential relative to lithium metal similar to graphite. However, elemental silicon undergoes a very large volume change upon alloying with lithium. Large volume expansions on the order of 2-4 times or more of the initial volume have been observed, and the large volume changes are associated with a significant decrease in the cycling stability of batteries with silicon-based anodes.

[0077] The cells described herein can use commercially available silicon suboxide, elemental silicon and carbon composites. Other formulations of silicon-based negative electrode active materials have also been developed that provide high capacity and suitable cycling properties. Below are described several silicon-based compositions that may provide promising alternatives to commercially available SiO-based compositions. The improved electrolyte formulations described herein have been found to be particularly effective with silicon-based negative electrode active materials and blends of silicon-based active materials with graphite.

[0078] Also, silicon-based high capacity materials in the negative electrode of a lithium-based battery may, in some formulations, exhibit a large irreversible capacity loss (IRCL) in the first charge / discharge cycle of the battery. The high IRCL of a silicon-based anode may consume a significant portion of the capacity available for the energy output of the battery. Since the cathode, i.e., the positive electrode, supplies all the lithium in a conventional lithium-ion battery, a high IRCL in the anode, i.e., the negative electrode, may result in a low energy battery. To compensate for the large anode IRCL, complementary lithium may be added directly or indirectly to the negative electrode material to compensate for the IRCL. The use of complementary lithium to improve the performance of silicon-based electrodes is also described in the '694 patent and the '228 patent, both of which are incorporated herein by reference. The use of complementary lithium in improved battery designs is further described below.

[0079] The anode, or negative electrode, of the battery described herein can use nanostructured active silicon-based materials to better accommodate volume expansion and thus maintain mechanical electrode stability and battery cycle life. Nanostructured silicon-based negative electrode compositions are disclosed in the '694 application, the '228 patent, and U.S. Pat. No. 9,139,441 to Anguchamy et al., entitled "Porous Silicon Based Anode Material Formed Using Metal Reduction" ('441 patent), which is incorporated herein by reference. Suitable nanostructured silicon can include, for example, nanoporous silicon and nanoparticulate silicon. Nanostructured silicon can also be formed into composites with carbon and / or alloys with other metallic elements. The goal of the design of improved silicon-based materials is to further stabilize the negative electrode material on cycling while maintaining high specific capacity and, in some embodiments, reducing irreversible capacity loss in the first charge and discharge cycle. Additionally, pyrolytic carbon coatings have also been observed to stabilize silicon-based materials with respect to battery performance.

[0080] Desirable high capacity anode active materials may include porous silicon (pSi)-based materials and / or composites of porous silicon-based materials. In general, pSi-based materials include highly porous crystalline silicon that can provide high surface area and / or high porosity relative to bulk silicon. Although nanostructured porous silicon can be formed by a variety of approaches, such as electrochemical etching of silicon wafers, particularly good battery performance has been obtained from nanostructured porous silicon obtained by metal reduction of silicon oxide powder. In particular, the material has particularly good cycling properties while maintaining a high specific capacity. Formation of composites of pSi-based materials with carbon-based materials or metals can further mechanically stabilize the anode for improved cycling. Additional description of pSi-based materials from reduction of silicon oxide can be found in the '441 patent referenced above.

[0081] With respect to composites, nanostructured silicon components can be combined with, for example, carbon nanoparticles and / or carbon nanofibers in an intimate composite. The components can be, for example, ground to form a composite in which the materials are intimately associated. In general, such associations are believed to have mechanical characteristics such as softer silicon coated on or mechanically fixed to a harder carbon material. In additional or alternative embodiments, silicon can be ground together with metal powders to form alloys that may have corresponding nanostructures. Carbon components can be combined with silicon-metal alloys to form multi-component composites.

[0082] Also, a carbon coating can be applied on the silicon-based material to improve electrical conductivity. The carbon coating also appears to stabilize the silicon-based material with respect to improved cycling and reduced irreversible capacity loss. The desired carbon coating can be formed by pyrolyzing an organic composition. The organic composition can be pyrolyzed at relatively high temperatures, for example, about 800°C to about 900°C, to form a hard amorphous coating. In some embodiments, the desired organic composition can be dissolved in a suitable solvent, such as water and / or a volatile organic solvent, for combination with the silicon-based component. This dispersion can be thoroughly mixed with the silicon-based composition. After drying the mixture to remove the solvent, the dried mixture with the silicon-based material coated with the carbon precursor can be heated in an oxygen-free atmosphere to pyrolyze the organic composition, such as organic polymers, some low molecular solid organic compositions, to form the carbon coating.

[0083] Similar to silicon, oxygen-deficient silicon oxides, such as silicon oxide, SiO x(0.1≦x≦1.9) can be intercalated / alloyed with lithium so that the oxygen-deficient silicon oxide can function as an active material in a lithium-ion battery. These oxygen-deficient silicon oxide materials are generally referred to as silicon oxide-based materials, and in some embodiments can contain various amounts of silicon, silicon oxide, and silicon dioxide. The oxygen-deficient silicon oxide can incorporate relatively large amounts of lithium so that the material can exhibit a large specific capacity. However, silicon oxide is generally observed to have a capacity that degrades rapidly with battery cycling, similar to that observed for elemental silicon.

[0084] Silicon oxide-based compositions can be formed into composites with high capacity and very good cycling properties, as described in the above-referenced '228 patent. In particular, oxygen-deficient silicon oxide can be surprisingly formed into composites with conductive materials, such as conductive carbon or metal powders, which significantly improve cycling while providing high specific capacitance values. Furthermore, milling silicon oxide into smaller particles, such as submicron structured materials, can further improve the performance of the material.

[0085] In general, a wide range of composites is available and may include silicon oxide, carbon components such as graphite particles (Gr), inert metal powders (M), elemental silicon (Si), especially nanoparticles, pyrolytic carbon coatings (HC), carbon nanofibers (CNF), or combinations thereof. The component structure may or may not correspond to the structure of the components within the composite. Thus, the general composition of the composite can be expressed as αSiO-βGr-χHC-δM-εCNF-φSi, where α, β, χ, δ, ε, and φ are relative weights that may be selected such that α+β+χ+δ+ε+φ=1. In general, 0.35<α<1, 0≦β<0.6, 0≦χ<0.65, 0≦δ<0.65, 0≦ε<0.65, and 0≦φ<0.65. Certain subsets of these composite ranges are of particular interest. In some embodiments, a composite of SiO and one or more carbon-based components is desired and can be represented by the formula αSiO-βGr-χHC-εCNF, where 0.35<α<0.9, 0≦β<0.6, 0≦χ<0.65, and 0≦ε<0.65 (δ=0 and φ=0); in further embodiments, 0.35<α<0.8, 0.1≦β<0.6, 0.0≦χ<0.55, and 0≦ε<0.55; in some embodiments, 0.35<α<0.8, 0≦β<0.45, 0.0≦χ<0.55, and 0.1≦ε<0.65, and in additional embodiments, 0.35<α<0.8, 0≦β<0.55, 0.1≦χ<0.65, and 0≦ε<0.55. In additional or alternative embodiments, a composite of SiO, an inert metal powder, and optionally one or more conductive carbon components can be formed, which can be represented by the formula αSiO-βGr-χHC-δM-εCNF, where 0.35<α<1, 0≦β<0.55, 0≦χ<0.55, 0.1≦δ<0.65, and 0≦ε<0.55.In further additional or alternative embodiments, a composite of SiO and elemental silicon and optionally one or more conductive carbon components can be formed, which can be represented by the formula αSiO-βGr-χHC-εCNF-φSi, where 0.35<α<1, 0≦β<0.55, 0≦χ<0.55, 0≦ε<0.55 and 0.1≦φ<0.65, and in further embodiments, 0.35<α<1, 0≦β<0.45, 0.1≦χ<0.55, 0≦ε<0.45 and 0.1≦φ<0.55. One of ordinary skill in the art will recognize that additional ranges within the explicit ranges above are contemplated and are within the present disclosure. As used herein, the reference to a composite refers to the application of significant binding forces, such as HEMM milling, to intimately associate the materials, as opposed to a simple blend, which would not be considered to form a composite.

[0086] Various Si-SiO x A solution-based approach for the synthesis of SiO-CM (M=metal) composites is described in U.S. Patent Application Publication No. 2014 / 0308585 to Han et al., entitled "Silicon-Based Active Materials for Lithium Ion Batteries and Synthesis With Solution Processing," which is incorporated herein by reference. Silicon-based carbon composites using graphene sheets are described in U.S. Patent Application Publication No. 2014 / 0370387 to Anguchamy et al., entitled "Silicon-Silicon Oxide-Carbon Composites For Lithium Battery Electrodes and Methods for Forming the Composites," which is incorporated herein by reference. x -Si-C or SiO x Commercially available materials believed to include -Si composites are used in the example batteries.

[0087] The capacity of the anode significantly affects the energy density of the battery. The higher the specific capacity of the anode material, the lower the weight of the anode in the same power cell. When the negative electrode is made of a silicon-based material, the electrode can have a discharge specific capacity at C / 3 rate of about 800 mAh / g to 2500 mAh / g at 1.5 V to 5 mV vs. lithium metal, about 900 mAh / g to about 2300 mAh / g in further embodiments, and about 950 mAh / g to about 2200 mAh / g in other embodiments. A person of ordinary skill in the art will recognize that additional ranges of discharge specific capacity within the explicit ranges above are contemplated and are within the present disclosure.

[0088] positive electrode Using the improved negative electrodes, various positive electrode chemistries can be effectively implemented. Selected compositions can be blended into the positive electrode with appropriate binders and conductive materials. This section focuses on positive electrode active materials that are particularly desirable for high voltage cycling and reasonably high capacity. This section also describes the overall electrode composition and properties.

[0089] The desired application of the final cell may influence the selection of the positive electrode composition to some extent. In this regard, a wide range of compositions are described below. For automotive and similar applications, certain positive electrode chemistries have been found to be desirable for achieving high energy density together with cycling over 600 cycles while maintaining at least 80% capacity, although some materials show promising results with somewhat lower cycling stability. In particular, nickel-rich lithium nickel manganese cobalt oxide provides very long cycling performance based on the improved electrolyte described herein. In another embodiment, blending a blend of nickel-rich lithium nickel manganese cobalt oxide and (lithium + manganese) rich lithium nickel manganese cobalt oxide provides desirable positive electrode performance. Furthermore, nickel-rich lithium nickel manganese cobalt oxide alone as an active material can provide desirable high energy density with average discharge voltage with good cycling when combined with the silicon-based negative electrode described herein. Below, an example is given for nickel-rich lithium nickel manganese cobalt oxide alone.

[0090] Nickel-rich lithium nickel manganese cobalt oxide (N-NMC) can provide desirable cycling and capacity characteristics for the lithium-ion batteries described herein. In particular, nickel-rich compositions have the formula LiNi x Mn y Co zO2, where x+y+z≈1, 0.45≦x, 0.025≦y, z≦0.35, and in further embodiments 0.50≦x, 0.03≦y, z≦0.325, and 0.55≦x, 0.04≦y, z≦0.3. The amount of nickel can affect the selected charging voltage to balance cycling stability and discharge energy density. For values ​​of x in the range of 0.525≦x≦0.7, the selected charging voltage can be 4.25V to 4.375V. For values ​​of x in the range of 0.7≦x≦0.9, the selected charging voltage can be 4.05V to 4.325V. One of ordinary skill in the art will recognize that additional ranges of compositions and selected charging voltages within the explicit ranges above are contemplated and are within the present disclosure. These compositions have been found to provide relatively stable higher voltage cycling, good capacity, and desirable impedance. N-NMC powders can be synthesized using techniques such as the co-precipitation method described further below, and are commercially available from, for example, BASF (Germany), TODA (Japan), L&F Materials Corp. (Korea), Umicore (Belgium), and Jinhe Materials Corp. (China).

[0091] For N-NMC compositions, as the amount of nickel increases, the average voltage tends to be slightly higher, but the charge voltage for stable cycling tends to be slightly lower as the amount of nickel increases. Thus, while N-NMC active materials can provide good cycling and reasonably high capacity and energy density, the choice of active material can come at a cost.

[0092] As mentioned above, a desirable blend can include N-NMC and (lithium-rich + manganese-rich) lithium nickel manganese cobalt oxide (LM-NMC or HCMR®). These compositions have the formula Li 1+b Ni α Mn β Co γ A δ O2-z F z (wherein b+α+β+γ+δ≈1, b is in the range of about 0.04 to about 0.3, α is in the range of 0 to about 0.4, β is in the range of about 0.2 to about 0.65, γ is in the range of 0 to about 0.46, δ is in the range of about 0 to about 0.15, and z is in the range of 0 to 0.2, with the proviso that α and γ are not both 0, and A is a metal other than lithium, manganese, nickel, and cobalt). In some embodiments, A can be Mg, Sr, Ba, Cd, Zn, Al, Ga, B, Zr, Ti, Ca, Ce, Y, Nb, Cr, Fe, V, or combinations thereof. In additional or alternative embodiments, Li 1+b Ni α Mn β Co γ A δ O2 (where 0.05≦b≦0.125, 0.225≦α≦0.35, 0.35≦β≦0.45, 0.15≦γ≦0.3, 0≦δ≦0.05) and up to 5 mole percent of the oxygen can be replaced with a fluorine dopant. A person of ordinary skill in the art will recognize that additional ranges of compositions within the explicit ranges above are contemplated and are within the present disclosure. As described in U.S. Pat. No. 8,928,286 to Amiruddin et al., entitled "Very Long Cycling of Lithium Batteries With Lithium Rich Cathode Materials," which is incorporated herein by reference, long-term cycling stability has been achieved at relatively high cycling voltages for (lithium + manganese) rich NMC active materials.

[0093] LM-NMC cathode materials can be conveniently synthesized by co-precipitation and sol-gel processes detailed in the '160 and '873 patents. In some embodiments, the cathode materials are synthesized by precipitating mixed metal hydroxide or carbonate compositions from a solution containing +2 cations, where the hydroxide or carbonate composition has a selected composition. The metal hydroxide or carbonate precipitate is then subjected to one or more heat treatments to form a crystalline layered lithium metal oxide composition. The carbonate co-precipitation process described in the '873 patent has yielded desirable lithium-rich metal oxide materials with cobalt in the composition and high specific capacity performance with excellent tap density. These patents also describe the effective use of metal fluoride coatings to improve performance and cycling.

[0094] It has been found that for LM-NMC positive electrode active materials, the application of a coating on the material can improve the performance of the corresponding cell. Suitable coating materials, which are generally considered to be electrochemically inactive during battery cycling, may include metal fluorides, metal oxides, or non-fluoride halides of metals. The following LM-NMC example results are obtained with LM-NMC materials coated with metal fluorides. Improved metal fluoride coatings with appropriately designed thicknesses are described in published U.S. Patent No. 9,843,041 to Lopez et al., entitled "Coated Positive Electrode Materials for Lithium Ion Batteries," which is incorporated herein by reference. Suitable metal oxide coatings are further described, for example, in U.S. Patent No. 8,535,832 B2 to Karthikeyan et al., entitled "Metal Oxide Coated Positive Electrode Materials for Lithium-Based Batteries," which is incorporated herein by reference. The discovery of non-fluoride metal halides as desirable coatings for cathode active materials is described in U.S. Pat. No. 8,663,849 B2 to Venkatachalam et al., entitled "Metal Halide Coatings on Lithium Ion Battery Positive Electrode Materials and Corresponding Batteries," which is incorporated herein by reference.

[0095] With respect to the active material blend for the positive electrode, the active material can include about 3% to about 85% by weight LM-NMC, in further embodiments about 5% to about 75% by weight LM-NMC, in additional embodiments about 6% to about 70% by weight LM-NMC, and in other embodiments about 7% to about 65% by weight LM-NMC. Similarly, in the positive electrode active material blend, the active material can include about 15% to about 97% by weight N-NMC, in further embodiments about 25% to about 95% by weight, in additional embodiments about 30% to about 94% by weight, and in other embodiments about 35% to about 93% by weight N-NMC. The positive electrode active material can optionally include 0 to 25% by weight lithium cobalt oxide, LiNi 0.33 Mn 0.33 Co 0.33 O2(NMC111), LiNi 0.8 Co 0.15 Al 0.05 O2(NCA), mixtures thereof, and the like. A person of ordinary skill in the art will recognize that additional ranges of composition blends within the explicit ranges above are contemplated and are within the present disclosure.

[0096] As described above, the positive electrode generally includes an active material and a conductive material in a binder. The loading of active material in the electrode can be large. In some embodiments, the positive electrode includes about 85 to about 99% of the positive electrode active material, in other embodiments about 90 to about 98% of the positive electrode active material, and in further embodiments about 95 to about 97.5% of the positive electrode active material. In some embodiments, the positive electrode has about 0.75 to about 10% of the polymer binder, in other embodiments about 0.8 to about 7.5% of the polymer binder, and in further embodiments about 0.9 to about 5% of the polymer binder. In general, the positive electrode composition can also include a conductive additive different from the electroactive composition. In some embodiments, the positive electrode can have 0.4% to about 12% by weight of the conductive additive, in further embodiments about 0.45% to about 7% by weight, and in other embodiments about 0.5% to about 5% by weight of the conductive additive. A person of ordinary skill in the art will recognize that additional ranges of particle loadings within the explicit ranges above are contemplated and are within the present disclosure. The active materials for the positive electrode are described above. Suitable polymer binders for the positive electrode include, for example, polyvinylidene fluoride, polyethylene oxide, polyimide, polyethylene, polypropylene, polytetrafluoroethylene, polyacrylate, rubber, such as ethylene-propylene-diene monomer (EPDM) rubber or styrene butadiene rubber (SBR), copolymers thereof, or mixtures thereof. For the positive electrode, polyvinylidene fluoride (pvdf) can be used with good results, and the example positive electrode uses a pvdf binder. Conductive additives have been described in detail for the negative electrode, and nanoscale conductive carbon can be effectively used for the positive electrode.

[0097] For a particular loading level, electrode density (of active material) is inversely proportional to thickness, so that electrodes with higher density will be thinner than electrodes with lower density. The loading is equal to density multiplied by thickness. In some embodiments, the battery positive electrode has a loading of about 10 to about 40 mg / cm. 2 and about 12 mg / cm in other embodiments. 2~Approx. 37.5mg / cm 2 and in additional embodiments, about 13 mg / cm 2 ~about 35mg / cm 2 and 20 mg / cm in other embodiments. 2 ~Approx. 32.5mg / cm 2 In some embodiments, the positive electrode of the battery has an active material density of from about 2.5 g / cc to about 4.6 g / cc in some embodiments, from about 3.0 g / cc to about 4.4 g / cc in other embodiments, and from about 3.25 g / cc to about 4.3 g / cc in additional embodiments. In further embodiments, the positive electrode can have a thickness of positive electrode material on each side of the current collector, after pressing and drying, of from about 45 microns to about 300 microns, from about 80 microns to about 275 microns in some embodiments, and from about 90 microns to about 250 microns in additional embodiments. One of ordinary skill in the art will recognize that additional ranges of active material loading levels, electrode thicknesses, and electrode densities within the explicit ranges above are contemplated and are within the present disclosure.

[0098] Complementary Lithium The improved high energy battery design described herein generally includes supplemental lithium, and this section relates to approaches for incorporating supplemental lithium for suitable embodiments. In general, for cells using silicon-based negative electrode active materials, the incorporation of supplemental lithium is desirable because the material exhibits relatively high irreversible capacity loss during initial charging of the battery. Additionally, the supplemental lithium surprisingly stabilizes cycling of LM-NMC. Although various approaches can be used for the introduction of supplemental lithium into the battery, after the corresponding initial reaction and / or charging, the negative electrode is associated with an excess amount of lithium for cycling from the supplemental lithium. For the negative electrode in a battery with supplemental lithium, the structure and / or composition of the negative electrode may change compared to its initial structure and composition after the first cycle and after additional cycles.

[0099] Depending on the approach for the introduction of complementary lithium, the positive electrode may initially contain a source of complementary lithium and / or a sacrificial electrode containing complementary lithium may be introduced. Additionally or alternatively, the complementary lithium may be associated with the negative electrode. In some embodiments, the complementary lithium may be introduced to the negative electrode using electrochemical methods as opposed to purely chemical or mechanical methods. If the complementary lithium is initially placed in the positive electrode or another electrode, the negative electrode may be in an unchanged form without the presence of lithium until the battery is charged, or at least until the circuit between the negative electrode and the electrode with the complementary lithium is closed in the presence of the electrolyte and separator. For example, the positive electrode or complementary electrode may contain elemental lithium, lithium alloys and / or other sacrificial lithium sources in addition to other electrode components.

[0100] When the positive electrode includes sacrificial lithium, the lithium of the sacrificial lithium source is loaded into the negative electrode during the charging reaction. The voltage during charging based on the sacrificial lithium source may be significantly different from when charging is performed based on the positive electrode active material. For example, the elemental lithium in the positive electrode may react by oxidation of elemental lithium as long as the circuit is closed, so that the negative electrode active material can be charged without applying an external voltage. For some sacrificial lithium source materials, an external voltage is applied to oxidize the sacrificial lithium source in the positive electrode and promote lithium into the negative electrode active material. Charging can generally be performed using constant current, stepwise constant voltage charging, or other convenient charging schemes. However, at the end of the charging process, the battery should be charged to the desired voltage, which then requires the extraction (e.g., deintercalation and dealloying) of lithium from the positive electrode active material.

[0101] In further embodiments, at least a portion of the complementary lithium is first associated with the negative electrode. For example, the complementary lithium can be in the form of a lithium alloy or other lithium source that is more electronegative than the negative electrode active material. The elemental lithium can be in the form of a thin film, lithium alloy foil, and / or powder, such as those formed by vapor deposition, sputtering, or ablation. Elemental lithium, especially in powder form, can be coated to stabilize the lithium for handling purposes. Commercially available lithium powders, such as powders from Livent Corporation, are sold with a proprietary coating for stability. This coating generally does not change the performance of the lithium powder for electrochemical applications. After contacting the negative electrode with the electrolyte, a reaction can occur and the complementary lithium is transported to the negative electrode active material. Because the electrodes are internally conductive, there is no need to close the circuit to obtain electron flow from the reaction. During this process, a solid electrolyte interface (SEI) layer can also be formed. Thus, the complementary lithium is loaded into the negative electrode active material, at least a portion of which is generally consumed in the formation of the SEI layer. The complementary lithium placed in the negative electrode should be more electronegative than the negative electrode active material so that application of a voltage will not cause the active material and the complementary lithium source to react in the same electrode.

[0102] In some embodiments, the complementary lithium associated with the negative electrode can be incorporated as a powder within the negative electrode. In particular, the negative electrode can include an active negative electrode composition, a complementary lithium source in a polymer binder matrix, and, if present, a conductive powder. In additional or alternative embodiments, the complementary lithium is disposed along the electrode surface. For example, the negative electrode can include an active layer having an active negative electrode composition and a complementary lithium source layer on the surface of the active layer. The complementary lithium source layer can include a lithium or lithium alloy foil sheet, a complementary lithium powder in a polymer binder, and / or particles of a complementary lithium source material disposed on the surface of the active layer. In alternative configurations, the complementary lithium source layer is between the active layer and the current collector. Also, in some embodiments, the negative electrode can include a complementary lithium source layer on both surfaces of the active layer.

[0103] The arrangement for carrying out the electrochemical preloading of lithium may include an electrode having a silicon-based active material formed on a current collector, which is placed in a container containing an electrolyte and a sheet of lithium source material in contact with the electrode. The sheet of lithium source material may include a lithium foil, a lithium alloy foil, or a lithium source material in a polymer binder, optionally with a conductive powder, which is in direct contact with the negative electrode preloaded with lithium so that electrons can flow between the materials to maintain electrical neutrality while the respective reactions are occurring. In a subsequent reaction, lithium is loaded into the silicon-based active material via intercalation, alloying, etc. In an alternative or additional embodiment, it is possible to mix the negative electrode active material in the electrolyte and the lithium source material for complementary lithium incorporation prior to formation into an electrode with a polymer binder, so that the respective materials can react spontaneously in the electrolyte.

[0104] In some embodiments, the lithium source in the electrode can be assembled into a cell together with the electrode preloaded with lithium. A separator can be placed between each electrode. A current can be passed between the electrodes to provide a controlled electrochemical prelithiation. Depending on the composition of the lithium source, it may or may not be necessary to apply a voltage to drive the lithium deposition in the silicon-based active material. An apparatus for carrying out such a lithiation process can include a container that holds an electrolyte and a cell that includes an electrode that will be used as the negative electrode in the final battery, a current collector, a separator, and a sacrificial electrode that includes a lithium source such as lithium metal foil. The separator is between the sacrificial electrode and the electrode with the silicon-based active material. Convenient sacrificial electrodes can include lithium foil, lithium powder embedded in a polymer, or lithium alloys, although any electrode with extractable lithium can be used. The container of the lithiation cell can include a conventional battery housing, a beaker, or any other convenient structure. This configuration has the advantage that the current can be measured to determine the degree of lithiation of the negative electrode. Additionally, the negative electrode can be cycled one or more times, with the negative electrode active material being loaded to near full loading with lithium. In this manner, the SEI layer can be formed with a desired degree of control during preloading of the negative electrode active material with lithium. The negative electrode is then fully formed during preparation of the negative electrode with a selected preloading with lithium.

[0105] Generally, for embodiments in which complementary lithium is used, the amount of complementary lithium preloaded or loadable into the active composition can be at least about 2.5% of the capacity, in further embodiments about 3% to about 55% of the capacity, in additional embodiments about 5% to about 52.5% of the capacity, and in some embodiments about 5% to about 50% of the negative electrode active material capacity. The complementary lithium can be selected to generally balance the IRCL of the negative electrode, although other amounts of complementary lithium can be used as desired. In some embodiments, the complementary lithium is added in an amount having an oxidation capacity corresponding to 60% to 180% of the first cycle IRCL of the negative electrode, in further embodiments, this is 80% to 165%, and in other embodiments, this is 90% to 155%. A person of ordinary skill in the art will recognize that additional ranges of percentages within the explicit ranges above are contemplated and are within the present disclosure. Thus, by the addition of complementary lithium, the contribution to the IRCL of the negative electrode can be effectively reduced or eliminated such that the measured IRCL of the battery represents a partial or majority contribution from the IRCL of the positive electrode that is not reduced by the presence of complementary lithium. A person of ordinary skill in the art will recognize that additional ranges of IRCL within the explicit ranges above are contemplated and are within the present disclosure.

[0106] Cathode and anode balance It has been found that the overall performance of a battery depends on the capacity of both the negative and positive electrodes and their relative balance. It has been found that the balance of electrodes is important in terms of achieving particularly high energy density and good cycling characteristics for the battery. In some embodiments, a sacrifice may be made in terms of achieving longer cycling stability and energy density. To achieve longer cycling stability, it may be desirable to balance the battery to achieve a relatively low energy density, but to use a battery that is suitable for stable long-term use in a wider range of operating parameters. With properly selected active materials, a desired electrode design, and an improved electrolyte formulation, high energy density is still obtainable while obtaining cycling of more than 800 cycles with a capacity fade of 80% or less. Electrode balance can be evaluated in several different ways, which can work effectively when the specific evaluation approach is properly considered.

[0107] Testing of the active materials is carried out in lithium cells that use lithium metal electrodes. Such cells are commonly referred to as half cells, in contrast to lithium-ion cells (called full cells) in which both electrodes contain lithium alloy or intercalation materials. In half cells that use silicon-based electrodes, the lithium electrode functions as the negative electrode and the silicon-based electrode functions as the positive electrode, as opposed to its usual role as the negative electrode in lithium-ion cells.

[0108] The positive electrode active material capacity can be estimated from the capacity of the material, which can be measured by cycling the material against lithium metal foil. For example, for a given positive electrode, the capacity can be evaluated by determining the insertion and extraction capacity during the first charge / discharge cycle. Lithium is then de-intercalated or extracted from the positive electrode to a selected voltage based on the material chemistry and the selected charging voltage of the cell design (typically 4.2V to 4.5V), and intercalated or inserted back into the positive electrode at a rate of C / 20 to 2V with a small adjustment, typically 0.1V, to a higher charging voltage vs. lithium metal based on the voltage of the final anode vs. lithium metal. Similarly, for a given silicon-based electrode, the insertion and extraction capabilities can be evaluated using a battery having a positive electrode with a silicon-based active material and a lithium foil negative electrode. This capacity is evaluated by determining the insertion and extraction capacity of the battery during the first charge / discharge cycle, in which lithium is intercalated / alloyed into the silicon-based electrode to 5 mV and de-intercalated / de-alloyed to 1.5 V at a rate of C / 20. In actual use, the observed capacity may vary from the tested capacity due to various factors such as high rate operation and changes in voltage range, which may be due to the battery design and the composition of the counter electrode, which is not lithium metal. For some evaluation approaches, the subsequent capacity after the first cycle can be used to evaluate the electrode balance, and higher discharge rates such as C / 3 or C / 10 can be used if necessary. The use of a balance after the formation cycle or several formation cycles may be desirable in that the balance is more based on the conditions during battery use.

[0109] In most commercially available carbon-based batteries, an excess of about 7-10% anode over cathode is used to prevent lithium plating. One major concern with excess anode is that it increases the cell weight, lowering the cell's energy density. Compared to graphite, which has a first cycle IRCL of about 7%, high capacity silicon-based anodes can have an IRCL ranging from about 10% to about 40%. A large portion of the capacity may be inactive in the cell after the first charge-discharge cycle, adding significant deadweight to the battery.

[0110] For high capacity anode materials, the negative electrode irreversible capacity loss is generally greater than the positive electrode irreversible capacity loss, which results in additional lithium availability for the cell. If the negative electrode has a significantly higher irreversible capacity loss than the positive electrode, the initial charge of the negative electrode will consume lithium irreversibly, so that during subsequent discharge, the negative electrode cannot supply enough lithium to provide the positive electrode with enough lithium to meet the full lithium acceptance capacity of the positive electrode. This results in wasted positive electrode capacity and a corresponding increase in weight that does not contribute to cycling. Most or all of the lithium loss from the net IRCL (negative electrode IRCL-positive electrode IRCL) can be made up by complementary lithium as described above. The evaluation of the electrode balance during the first formation cycle may or may not take complementary lithium into account. In the formation cycle or in subsequent cycles several cycles later, any excess amount of complementary lithium that is not consumed for IRCL is generally alloyed into the anode material. The electrode balance can be evaluated during a cycling stage after formation, such as the fourth cycle at a selected rate, and these capacities can be estimated from the electrode performance.

[0111] In terms of providing stable longer term cycling performance, it may be desirable to balance the electrodes to effectively use both electrode capacities and to avoid plating of lithium metal during cycling. Generally, electrode balance is considered during assembly of the electrodes with reference to the initial capacity of the electrodes relative to lithium metal.

[0112] Generally, the battery life can be selected to end when the energy output at a constant discharge rate drops by about 20% from the initial capacity, but other values ​​can be selected as necessary. For the materials described herein, the capacity drop due to cycling of the negative electrode is generally greater than that of the positive electrode, so avoiding lithium metal deposition due to cycling suggests a higher excess capacity of the negative electrode to further stabilize cycling. Generally, if the negative electrode capacity decreases about twice as fast as the positive electrode capacity, it may be desirable to include at least 10% additional negative electrode capacity to accommodate cycling. In a robust battery design, at least about 10% additional negative electrode may be desirable in various discharge conditions. In general, the balance can be selected such that the initial negative electrode charge capacity, evaluated at a C / 20 rate from open circuit voltage to 1.5 V vs. lithium, is about 110% to about 195%, in further embodiments about 120% to about 185%, and in additional embodiments about 130% to about 190% of the sum of the initial positive electrode charge capacity at a C / 20 rate from open circuit to the charge voltage of the cell design (generally 4.2 V to 4.6 V) plus the oxidation capacity of any complementary lithium. Alternatively, the electrode balance can be evaluated at the fourth cycle at a C / 10 or C / 3 discharge rate with the negative electrode capacity relative to the positive electrode capacity being about 110% to about 195%, in further embodiments about 120% to about 185%, and in additional embodiments about 130% to about 190%. One of ordinary skill in the art will recognize that additional ranges of balance within the above explicit ranges are contemplated and are within the present disclosure. Such balance is described in the battery designs described below.

[0113] Performance characteristics The improved electrolyte formulation described herein can further extend the cycling improvement obtained by the negative electrode design, which is particularly effective for silicon-based materials.The combination of design features described herein can provide longer cycling stability while maintaining desirable battery performance.The achievement of long-term cycling involves the use of the improved electrode design described herein, which has a balance of cell design parameters combined with the improved electrolyte formulation, which surprisingly further extends cycling with unprecedented stability.

[0114] The selected charging voltage may be influenced by the positive electrode active material. In general, the selected charging voltage for these cells is about 4.05V to 4.4V. The battery can exhibit very good cycling performance. In some embodiments, the battery can exhibit at least about 80% of the 6th cycle capacity when discharged at 1C rate from the selected charging voltage to 2.5V at 30°C in the 700th cycle, at least about 82% of the 6th cycle discharge capacity when cycled at C from the selected charging voltage to 2.5V at 30°C in the 700th cycle, and in other embodiments at least about 84% of the 6th cycle discharge capacity when cycled at C from the selected charging voltage to 2.5V at 30°C in the 700th cycle. Similarly, the battery may exhibit at least about 80% of the 6th cycle capacity when discharged at a 1C rate from the selected charge voltage to 2.5V at 30° C. at the 725th cycle, at least about 80% of the 6th cycle discharge capacity when cycled at C / 3 from the selected charge voltage to 2.5V at 30° C. at the 750th cycle, and in additional embodiments at least about 80% of the 6th cycle discharge capacity at the 800th cycle. Comparable results are obtained at 2C charge and discharge rates. A person of ordinary skill in the art will recognize that additional ranges within the explicit ranges above are contemplated and are within the present disclosure. EXAMPLES

[0115] General Methods and Materials. The electrolyte formulations were tested by their incorporation into coin cells using an NMC positive electrode and a negative electrode incorporating a blend of silicon oxide-based composite and graphite as the active material. In particular, the active material of the positive electrode was a 0.01% NMC based composite of the formula LiNi 0.6 Mn 0.2 Co 0.2 O2(NMC622) or LiNi 0.8 Mn 0.1 Co 0.1 The negative electrode active material was a commercially available lithium nickel manganese cobalt oxide with O2 (NMC811). The negative electrode active material was a commercially available SiO-Si-C (SiOx) composite blended with electrochemically active graphite.

[0116] To form a negative electrode using a silicon oxide-based active material, the active material is, unless otherwise specified, 65% to 80% by weight of a commercially available silicon oxide / silicon / carbon composite (herein referred to as SiO x The negative electrodes were formed by blending powders of SiO2 / Si / C (denoted as SiO2 / Si / C) with the remainder (20 wt%-35 wt%) of graphite (KS 6 composite graphite, Imerys). The negative electrode active material was thoroughly mixed with 1 wt%-7 wt% of nanoscale carbon conductive additive to form a homogenous powder mixture. The negative electrodes had 2-6 wt% carbon nanotubes as conductive additive. The powder components of the electrode, active material, and carbon nanotubes were mixed to form a homogenous powder mixture. The negative electrodes had 1-7 wt% lower modulus binder and 7-15% polyimide. The weight ratio of lower modulus binder to polyimide was 0.714.

[0117] To form the negative electrode, a blend of the polymer binder, polyimide binder, and low modulus binder was mixed with N-methylpyrrolidone ("NMP") (Sigma-Aldrich) and stirred overnight to form a polymer binder-NMP solution. The homogenous powder mixture was then added to the polymer binder-NMP solution and mixed for approximately 2 hours to form a homogenous slurry. The slurry was applied onto a copper foil current collector to form a wet film, and the laminated current collector was dried in a vacuum oven to remove the NMP and harden the polymer. The laminated current collector was then pressed between the rollers of a sheet mill to obtain the desired laminate thickness. The dried laminate contained 2-20% by weight of binder, with the remainder of the electrode contributed by the powder. The negative electrode was electrochemically prelithiated with sufficient lithium to compensate for 100%-160% of the lithium loss due to irreversible capacity loss of the anode.

[0118] The positive electrode had an active material loading of about 93-97.5 wt% blended with 1-4 wt% PVDF binder and 1-3 wt% nanoscale carbon. The cathode material was blended with NMP solvent and spread on an aluminum foil current collector, pressed, and dried.

[0119] To form coin cells, a portion of the negative electrode was cut to size along with a separator, and a portion of the positive electrode was also cut to size. The separator for these cells was Celgard® porous polymer membrane. The electrodes with the separator between them were placed into a coin cell housing. An electrolyte selected as described below was placed into the cell, and the cell was sealed.

[0120] The assembled cells were cycled from 4.3 V to 2.5 V for the NMC622 cells and from 4.2 V to 2.5 V for the NMC811 cells at 23° C. The cells were charged and discharged at a C / 10 rate in the first cycle, a C / 5 rate in the second cycle, and then cycled at a C / 3 rate.

[0121] Examples 8 and 9 relate to pouch cells, and the formation of these cells is further described below.

[0122] Example 1 – Cell with NMC cathode and commercial electrolyte This example demonstrates the cycling performance in coin cells with blends of NCM positive electrode active material, negative electrode active material, and a commercial electrolyte.

[0123] In the first combination of cells, the negative electrodes of these cells were as described in the Materials and Methods section above. The positive electrodes contained LiNi 0.8 Mn 0.1 Co 0.1 O2(NMC811) or LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622). Cells were formed with different loadings of the positive electrode active material. The NMC622 cells were cycled over a voltage range of either 4.30V to 2.5V or 4.35V to 2.5V, and the NMC811 cells were cycled over a voltage range of 4.20V to 2.5V.

[0124] An initial charge-discharge cycle was performed at a rate of C / 10, and the results for all samples are summarized in Table 1.

[0125] JPEG2025060873000004.jpg80169

[0126] Cells corresponding to samples C1-C8 were also cycled. In particular, the cells were charged and discharged at a C / 10 rate in the first cycle, a C / 5 rate in the second cycle, and then cycled at a C / 3 rate. Table 2 summarizes the rate capacities of the cell samples based on the discharge capacity at the stated discharge rates.

[0127] JPEG2025060873000005.jpg73165

[0128] The discharge capacity as a function of cycle for samples C2, C4, and C7 are plotted in Figure 5, and the normalized capacity as a function of cycle in Figure 6. The best cycling performance of these coin cells is the sample based on NMC622 cycled from 4.30 V to 2.5 V, while the worst cycling performance across the cycle range is based on NMC622 cycled from 4.35 V to 2.5 V.

[0129] Example 2 - Electrolyte formulation for silicon oxide based lithium ion cells This example provides a set of electrolyte formulations designed for silicon oxide-based active materials used in combination with NMC active materials along with their ionic conductivity measurements.

[0130] Electrolyte Formulations. Table 3 presents electrolyte formulations with various lithium hexafluorophosphate (LiPF6) concentrations and solvent contents. The LiPF6 concentration and weight percent ranges of fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), fluorobenzene (FB), propylene carbonate (PC), 1,3-propane sulfate (PS) and ethyl carbonate (EC) for each electrolyte formulation are shown in the table (percentages are volume percents with respect to the solvent), and the conductivity measurements (25°C) of each formulation are presented.

[0131] JPEG2025060873000006.jpg245169

[0132] Example 3 – Rate performance of electrochemical cells with selected electrolyte formulations This example demonstrates the rate performance achievable with selected electrolytes from Example 2.

[0133] Coin cells were formed as described above in Example 1, except that electrolytes selected from Table 3 were used. Table 4 shows the relationship between electrolyte conductivity and rate capability for the five electrolyte formulations in Table 3. The assembled cells were cycled after the first two formation cycles at different charge / discharge rates, e.g., 0.333C / 0.333C, 1C / 1C, and 2C / 1C, for electrolyte formulations nos. 1, 2, 3, 7, and 10.

[0134] JPEG2025060873000007.jpg65169

[0135] Example 4 – Electrolyte dependence on cycling performance of NMC622 / SiOx Li-ion cells The cycling performance of coin cells based on different electrolyte formulations is described in this example.

[0136] Effect of ethylene carbonate. Figures 7 (1C / 1C) and 8 (2C / 2C) show the detrimental effect on the rate performance of a lithium-ion battery system when the electrolyte formulation contains ethylene carbonate. The coin cells for this example are based on NMC622 positive electrode active material. The negative electrodes and coin cells were formed as described in Example 1. For example, for the coin cells with electrolyte No. 1 (Table 3), the rate performance of the system was significantly worse after adding ethylene carbonate to the formulation. In comparison with the commercial electrolytes (Product 1 and Product 2) listed in Table 3, formulations No. 1 and 2 containing 0% ethylene carbonate show superior performance in both 1C and 2C cycling. Electrolyte 1 showed somewhat better cycling performance compared to electrolyte 2.

[0137] Effect of fluoroethylene carbonate concentration. Figures 9 and 10 show normalized (Figure 9) and non-normalized (Figure 10) 1C charge and discharge cycling performance of coin cells containing electrolyte formulations with amounts of fluoroethylene carbonate varying from 0% to 30% by volume. The data show that at least 5-10% FEC additive is required to obtain more than 700 cycles to 80% capacity retention of silicon-based cells. Electrolytes with 10% or 15% FEC had the best cycling performance versus electrolytes with lower or higher amounts of FEC. Electrolytes without FEC cycled poorly.

[0138] Effect of Solvents. For 1C cycling applications, various amounts of dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate in the electrolyte formulations showed relatively consistent performance in battery cycle life, e.g., 765-805 cycles with 80% capacity retention in coin cells (Figures 11 (1C / 1C) and 12 (2C / 2C)), but the best results were obtained with at least some DMC and not too much DEC. However, for 2C cycling applications, cycling performance is affected by various solvent ratios. For example, when the electrolyte contains more than 70% DEC, cycling performance decreases. Although high weight percentages of either DMC or EMC do not adversely affect cycling performance, the best results were obtained with several blends of solvent components mixed with the room temperature liquid solvent component, i.e., FEC.

[0139] Effect of Solvent and Additives. The effect of fluorobenzene and propylene carbonate as additives was investigated. These are shown in Table 3 as electrolytes 12-14. In all tested additive formulations, coin cells showed consistent cycling performance, e.g., 770-780 cycles with 80% capacity retention (Figures 13 (normalized) and 14 (unnormalized capacity)). This result was also similar to the performance of the closest electrolyte without additive, electrolyte 7, as shown in Figure 11.

[0140] Example 5 – Cycling performance of NMC811 / SiOx coin cells This example shows the cycling performance with NMC811 active material in the positive electrode / cathode for one of the electrolytes developed for the silicon oxide based negative electrode active material.

[0141] Electrolyte 2 was also used to cycle coin cells similar to those described in Examples 1, 3 and 4, formulated with NMC811 positive electrode active material and SiOx negative electrode. These cells were cycled from 2.5V to 4.2V. The cycling performance is shown in Figures 15 (1C / 1C) and 16 (2C / 2C). The 1C and 2C coin cell applications provide higher cycling performance up to 700 cycles to 80% capacity retention when electrolyte 2 is used as the electrolyte. Although 1C / 1C cycles slightly better with respect to the NMC811 electrode and 2C / 2C cycles slightly worse with respect to the NMC811 electrode, the cycling performance is comparable to the NMC622 results.

[0142] Example 6 – Large capacity long term cycling battery with commercial electrolyte This example demonstrates the long-term cycling stability based on the improved negative electrode loaded into a large battery.

[0143] The pouch cell was designed with a target capacity of about 11 Ah. The prismatic pouch cell had approximate dimensions of 145 mm x 64 mm x 7.7 mm (thickness), excluding the tabs. The cell design is shown in Figures 17 and 18. The electrodes were formed as described in Materials and Methods above, and the separator sheet was pleated with the plated electrodes placed in the separator folds. The separator for the pouch cell was a porous polymer composite sheet with a gel-forming polymer coating. Supplemental lithium was provided by applying lithium powder (SLM®, Livent Corp.) to the negative electrode surface prior to assembly to roughly compensate for 100%-160% of the IRCL of the silicon-based negative electrode active material. The battery was designed to have a total capacity of about 11 Ah at 30°C with a discharge rate of C / 3. The battery was cycled at a charge and discharge rate of C / 20 for one formation cycle. The cells were then cycled at 30° C. at charge and discharge rates of C / 3.

[0144] The positive electrode is based on NMC811 and contains 75-90% by weight of SiO x 11 Ah cells were formed from the same anodes as those described above for the coin cells above, with NMC622-based cathodes with anodes having active materials of 10-25 wt% graphite / Si / C composites. Based on low-rate (C / 20) capacity, the anode capacity was initially 130-160% of the cathode capacity. The anode had a blend of polyimide, a lower modulus binder, and a carbon nanotube conductive material. A commercially available fluorinated electrolyte was also used. Two comparable representative cells were cycled from 4.3 V to 2.5 V for the cells with NMC622 cathodes. The cycling results are plotted in Figures 19 and 20. In Figures 19 and 20, the specific capacity and normalized specific capacity are plotted as a function of cycles.

[0145] For cells with NMC811 cathode, comparable cells were cycled at a rate of C / 3 from 4.15 V to 2.5 V and from 4.20 V to 2.5 V. The cycling results are plotted in Figures 21 and 22. In Figures 21 and 22, the specific capacity and normalized specific capacity are plotted as a function of cycles.

[0146] Example 7 – Cycling performance of NMC622 / SiOx pouch cells with improved electrolyte This example investigates the cycling performance of a pouch cell configuration with a silicon oxide based active material with the improved electrolyte described herein.

[0147] The cycling performance of NMC622 / SiOx-based 11 Ah 285 Wh / kg pouch cells was tested using three different electrolyte formulations from Table 3. The pouch cell structure was the same as that described in Example 6, but the electrodes and new electrolyte formulations were used, as described in the Materials and Methods section. Figures 23 and 24 show plots of normalized discharge capacity (Figure 23) and non-normalized discharge capacity (Figure 24) by electrolytes 2, 7, and 10. The cell formed by electrolyte 2 provides cycling performance of more than 1000 cycles to 80% capacity retention. For 1C pouch cell application, when compared with formulations no. 7 and 10, the results show that a weight percentage of 70% or more of DMC is preferred in electrolyte formulations containing LiPF6 and FEC.

[0148] Example 8 – Blended Positive Electrode Active Materials This example demonstrates the utility of the improved electrolyte for cycling with cells having positive electrodes with a blend of active materials.

[0149] A positive electrode was formed by blending nickel-rich lithium nickel manganese cobalt oxide (N-NMC) in combination with lithium plus manganese rich NMC (LM-NCM). It has been found that some LM-NMC compositions can exhibit relatively low DC resistance while maintaining relatively high capacity and excellent cycling, as described in U.S. Pat. No. 9,552,901 B2 to Amiruddin et al., entitled "Lithium Ion Batteries With High Energy Density, Excellent Cycling Capability and Low Internal Impedance" (hereinafter the '901 patent), which is incorporated herein by reference. The negative electrode was the same as that described in Example 2, and coin cells were formed as described in Example 2.

[0150] Cycling results were obtained for cells with five different electrolytes from Table 3, specifically electrolytes 1, 2, 3, 7 and 8. The cells were cycled from 4.25V to 2.3V at a rate of 1C / 1C-charge / discharge after the first cycle. The cycling results are plotted in Figures 25 (normalized capacity) and 26 (non-normalized discharge capacity). Similar cycling results were obtained for the electrolytes, except for electrolyte 1. Improved cycling was obtained for all electrolytes, compared to comparable results obtained with commercially available fluorinated electrolytes (see the '209 application above), with electrolytes 2, 3, 7 and 8 showing significantly better results. However, the cycling results were not as good as those for the N-NMC based cathode.

[0151] The above embodiments are illustrative and not limiting. Additional embodiments are within the scope of the claims. In addition, although the present invention has been described with reference to specific embodiments, those skilled in the art will recognize that changes in form and detail may be made without departing from the spirit and scope of the present invention. Any incorporation by reference of the above documents is limited to not incorporating subject matter contrary to the explicit disclosure of the present specification. To the extent that a particular structure, composition and / or process is described herein by components, elements, ingredients, or other divisions, the disclosure of the present specification is understood to encompass, unless otherwise specified, embodiments that include the particular embodiment, the particular component, element, ingredient, other division, or combination thereof, as set forth in this discussion, as well as embodiments that consist essentially of such particular component, ingredient, other division, or combination thereof, which may include additional features that do not alter the basic nature of the subject matter.

Claims

1. an anode comprising about 75% to about 92% by weight of active material, about 1% to about 7% by weight of nanoscale conductive carbon, and about 6% to about 20% by weight of a polymer binder, the active material comprising about 35% to about 95% by weight of a silicon oxide based material and about 5% to about 65% by weight of graphite; Formula LiNi x Mn y Co z O 2 wherein x+y+z≈1, 0.3≦x, 0.025≦y≦0.35, and 0.025≦z≦0.35; and a positive electrode comprising a lithium nickel cobalt manganese oxide, conductive carbon, and a polymer binder; a separator between the negative electrode and the positive electrode; an electrolyte comprising about 1 M to about 2 M lithium salt and a non-aqueous solvent, the non-aqueous solvent comprising at least about 5 volume percent fluoroethylene carbonate and at least about 25 volume percent combined amounts of dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate; A container that encloses the other cell components; A lithium ion cell comprising:

2. 10. The lithium ion cell of claim 1, which can be cycled at a charge rate of 1C and a discharge rate of 1C for at least about 700 cycles without a capacity loss of more than 20% relative to the third cycle capacity.

3. The negative electrode active material comprises about 40% to about 90% by weight of a silicon oxide based material and about 10% to about 60% by weight of graphite, the graphite being about 2 m 2 / g ~ approx. 100m 2 3. The lithium ion cell of claim 1, having a BET surface area of ​​1.0-1.5 nm / g.

4. 4. The lithium-ion cell of claim 3, wherein the silicon oxide based material comprises a silicon-silicon oxide carbon composite material.

5. 5. The lithium ion cell of claim 1, wherein the polymer binder of the negative electrode comprises a blend of a polyimide and a second binder polymer selected from the group consisting of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, lithiated polyacrylic acid, copolymers thereof, and mixtures thereof.

6. 6. The lithium ion cell of claim 1, wherein the electrolyte comprises about 1.25 M to about 1.8 M lithium salt and the non-aqueous solvent comprises about 8 volume percent to about 25 volume percent fluoroethylene carbonate and dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate in a combined amount of at least about 50 volume percent.

7. 6. The lithium ion cell of claim 1, wherein the electrolyte further comprises about 2% to about 12% by weight propylene carbonate and about 2% to about 12% by weight fluorobenzene.

8. The lithium nickel manganese cobalt oxide has the formula LiNi x Mn y Co z O 2 8. The lithium ion cell of claim 1, wherein x+y+z≈1, 0.50≦x, 0.03≦y≦0.325, and 0.03≦z≦0.

325.

9. 9. The lithium ion cell of any one of claims 1 to 8, further comprising complementary lithium in an amount of about 80% to about 180% of the negative electrode first cycle irreversible capacity loss and having a ratio of negative electrode capacity divided by positive electrode capacity at the fourth cycle at a discharge rate of C / 3 of about 1.10 to about 1.

95.

10. The positive electrode comprises about 20% to about 80% by weight of a compound of the formula Li 1+b Ni α Mn β Co γ A δ O 2-z F z 10. The lithium-ion cell of claim 1, further comprising a (lithium+manganese) rich lithium metal oxide represented by the formula: where b+α+β+γ+δ≈1, b ranges from about 0.04 to about 0.3, α ranges from 0 to about 0.4, β ranges from about 0.2 to about 0.65, γ ranges from 0 to about 0.46, δ ranges from about 0 to about 0.15, and z ranges from 0 to 0.2, with the proviso that α and γ are not both 0, and A is a metal different from lithium, manganese, nickel, and cobalt.

11. an anode comprising about 75% to about 92% by weight of active material, about 1% to about 7% by weight of nanoscale conductive carbon, and about 6% to about 20% by weight of a polymer binder, the active material comprising about 40% to about 95% by weight of a silicon oxide based material and about 5% to about 60% by weight of graphite; Formula LiNi x M y Co z O 2 wherein x+y+z≈1, 0.3≦x, 0.025≦y≦0.35, 0.025≦z≦0.35, and M is Mn, Al, Mg, Sr, Ba, Cd, Zn, Ga, B, Zr, Ti, Ca, Ce, Y, Nb, Cr, Fe, V, or combinations thereof; and a positive electrode comprising a nickel-rich lithium nickel cobalt metal oxide, conductive carbon, and a polymer binder; a separator between the negative electrode and the positive electrode; an electrolyte comprising about 1 M to about 2 M lithium salt and a non-aqueous solvent, the non-aqueous solvent comprising at least about 5 volume percent fluoroethylene carbonate and at least about 25 volume percent combined amounts of dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate; A container that encloses the other cell components; 1. A lithium ion cell comprising:

12. 12. The lithium ion cell of claim 11, which can be cycled at a charge rate of 1C and a discharge rate of 1C for at least about 750 cycles without a capacity loss of more than 20% relative to the third cycle capacity.

13. The negative electrode active material comprises about 50% to about 90% by weight of a silicon oxide based material and about 10% to about 50% by weight of graphite, the graphite being about 2 m 2 / g ~ approx. 100m 2 13. The lithium ion cell of claim 11 or 12, having a BET surface area of ​​1.0-1.5 nm / g.

14. 14. The lithium-ion cell of claim 13, wherein the silicon oxide based material comprises a silicon-silicon oxide carbon composite material.

15. 15. The lithium ion cell of any one of claims 11 to 14, wherein the polymer binder of the negative electrode comprises a blend of a polyimide and a second binder polymer selected from the group consisting of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, lithiated polyacrylic acid, copolymers thereof, and mixtures thereof.

16. 16. The lithium ion cell of any one of claims 11-15, wherein the electrolyte comprises about 1.25 M to about 1.8 M lithium salt and the non-aqueous solvent comprises about 8 volume percent to about 25 volume percent fluoroethylene carbonate and dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate in a combined amount of at least about 50 volume percent.

17. 16. The lithium ion cell of claim 11, wherein the electrolyte further comprises about 2% to about 12% by weight propylene carbonate and about 2% to about 12% by weight fluorobenzene.

18. The lithium nickel cobalt oxide metal has the formula LiNi x Mn y Co z O 2 18. The lithium ion cell of any one of claims 11 to 17, generally represented by: where x+y+z≈1, 0.50≦x, 0.03≦y≦0.325, and 0.03≦z≦0.

325.

19. 19. The lithium ion cell of any one of claims 11-18, further comprising complementary lithium in an amount of about 80% to about 180% of the negative electrode first cycle irreversible capacity loss and having a ratio of negative electrode capacity divided by positive electrode capacity at the fourth cycle at a discharge rate of C / 3 of about 1.10 to about 1.

95.

20. 20. The lithium ion cell of any one of claims 11 to 19, which can be cycled at a charge rate of 1C and a discharge rate of 1C for at least about 800 cycles without a capacity loss of more than 20% relative to the third cycle capacity.

Citation Information

Patent Citations

  • Electrolyte solvent for improving battery safety and lithium secondary battery containing the same

    JP2007504628A

  • Negative electrode for lithium ion secondary battery and secondary battery using the same

    JP2011048969A

  • Secondary battery and vehicle mounted with the same

    JP2013182807A

  • Mixed active material for lithium secondary battery, positive electrode for lithium secondary battery, and lithium secondary battery

    JP2016119288A

  • Lithium ion battery

    JP2016167394A